GBIF Occurrence Download - Occdownload Gbif.Org (The Global Biodiversity Information Facility, 2018)
A dataset containing 737343565 species occurrences available in GBIF matching the query: Year: 1989-2018. The dataset includes 737343565 records from 15075 constituent datasets: 1626 records from Range table from planktonic foraminifers in ODP Hole 152-919A. 171 records from Large protozoan and small metazoan abundance measured on concentrated water bottle samples at station PS65/587-16. 99 records from Distribución histórica, prospección actual y áreas potenciales para reintroducir lobo mexicano (Canis lupus baileyi) en Durango, sur de la Sierra Madre Occidental, México. 19 records from Assemblage of living benthic foraminifera in sediment core CD146_55921#1, 63-150 µm. 36 records from Naturtag. 1 records from Description of Sweltsa tibetensis sp. n. (Plecoptera: Chloroperlidae) from Tibet Autonomous Region of China. 7122 records from MEXU/Leguminosae. 320 records from Waldstück Bremerhagen LK Bio Kl. 12. 235 records from Estimación de la densidad poblacional y dieta del lince (Lynx rufus) Sierra Seri, Sonora y Janos, Chihuahua. 81 records from Stomatopod Crustacea of the Austral and Gambier Islands, French Polynesia. 4 records from (Table 1) PBDE and BDE congener concentration in adipose tissue of East Greenland polar bears collected 1999-2001. 616 records from Range table from benthic foraminifers in ODP Hole 146-889A. 26058 records from Insect specimens in the Museum of Nature and Human Activities, Hyogo Prefecture, Japan. 1913 records from Estudio florístico de los bosques mesófilos de la Sierra Mazateca de Oaxaca, México. 742 records from Bannwald Burghauser Forst. 21 records from Sarcodine counts and carbon biomass at station TT007_8-CTD99. 39404 records from SEWBReC Bees, Wasps and Ants (South East Wales). 2 records from Araboplia lorisi new genus and species of Rutelinae from Saudi Arabia (Coleoptera, Scarabaeidae), with comments on the subtribe Popilliina. 2110 records from ZUEC-OPH - Coleção de Ophiuroidea do Museu de Zoologia da UNICAMP. 16 records from Revision of Lutnes Cameron (Hymenoptera: Eupelmidae). 43 records from Meiofauna densities from in situ feeding experiments in the Nazare Canyon conducted with sediments from ROV push-core JC10-95-PUC03. 116 records from COA Bird Collection (Arctos). 89 records from Great British Bee Count 2016 - Stage 2 (records verified from photo). 118 records from (Appendix A2) Cenomanian benthic foraminifera of ODP Site 207-1260. 336 records from Total foraminifera counts of multinet M33/1_MSN1029. 879 records from Bryophyte specimens of The Nagoya University Museum. 2 records from Beitrag zur Kenntnis der Höhlen-Oribatiden der Schweiz (Acari: Oribatida) (Neue und interessante Milben aus dem Genfer Museum LI). 1992 records from National Botanic Garden Belgium - Myxomycetes. 261 records from Artenvielfalt des "Grünen Klassenzimmers". 2628 records from Museu de Ciències Naturals de Barcelona: BGJBB. 4 records from Taxonomy of ant species (Hymenoptera: Formicidae) collected by pitfall traps from Sinai and Delta region, Egypt.. 336 records from Meiobenthic taxon counts from deep-sea in situ recolonization experiment I deployed at station PS64/474-1 during ARK-XIX/3c. 11189 records from Inventario florístico y entomofaunístico en tres objetos de conservación ecosistémicos en las zonas núcleo de las reservas estatales de Balam-kú y Balam-kin, Campeche. 2535 records from Plasm bearing foraminifera counts during METEOR cruise M36/5. 765 records from UWIZM Molluscs. 44 records from Abundance of non-diatom phytoplankton measured on water bottle samples at station PS58/041-2. 168 records from Plasm bearing foraminifera counts of multinet M12/3_MSN562. 6 records from The inaequalis species-group (Hymenoptera, Chrysididae, Chrysis) in China, with description of a new species. 38 records from Potamotrygon rex, a new species of Neotropical freshwater stingray (Chondrichthyes: Potamotrygonidae) from the middle and upper rio Tocantins, Brazil, closely allied to Potamotrygon henlei (Castelnau, 1855). 24 records from The genus Salfacarus (Acari: Opilioacarida) in Madagascar. 58 records from Abundance of non-diatom phytoplankton measured on water bottle samples at station PS58/091-4. 4621 records from Códigos de barras de la vida en peces y zooplancton de México. 7 records from The publication of primary biological events in the international GBIF (Global Biodiversity Information Facility) network: A case study with a small dataset of field collected occurrence samples of Buriti palms (Mauritia flexuosa).. 38550 records from Herbarium Specimens of Museum of Nature and Human Activities, Hyogo Pref., Japan. 8 records from Microplankton abundance in the euphotic zone of the Aegean Sea at Station JUNE-1998-IR50. 5 records from Loricifera - SMF. 353 records from (Table 4) Abundance of silicoflagellates and ebridians in selected samples from ODP Hole 138-847B. 30 records from Updated checklist of Balearic leaf beetles (Coleoptera: Chrysomelidae). 715041 records from KTP Ring Data. 49 records from Données naturalistes (Rhopalocères et Zygènes) de Bob WHITMARSH (indépendant). 6 records from Pseudotibiozus Demange, 1970 - millipedes of the Eastern Arc Mountains, Tanzania (Diplopoda, Spirostreptida, Spirostreptidae). 7055 records from Arbeitsgemeinschaft Heuschrecken Österreichs. 11 records from Données d'observation opportunistes collectées durant la campagne de prélèvements sédimentaires SHELL/CREOCEAN en Guyane française en 2013. Shell Exploration and Production France. 1 records from Synthèse de la Répartition des populations de cerf élaphe en 2000 (réseau Ongulés sauvages ONCFS-FNC-FDC). 2844 records from Australian Institute of Marine Science (AIMS) - Lizard Island Reef Biodiversity Expedition, Queensland, Australia (2008 - 2009). 609 records from (Table 3) Pleistocene nannofossil range chart for ODP Hole 134-831A. 46 records from Morphologische Daten von Natrix. 875 records from Caracterización biológica de la ventana de biodiversidad Montes de María, Municipio de Colosó, Sucre, Colombia. 190 records from BIRDRACE accipiter hardcore birding. 1 records from Orbinia wui, a new species from China, with redescription of O. dicrochaeta Wu, 1962 (Annelida, Orbiniidae). 5 records from LISU Herbario Angola. 6240 records from CNAC/Coleccion Nacional de Acaros. 229 records from Distribución y estructura poblacional de la tortuga de Berlandier, (Gopherus [=Xerobates] berlandieri) en México. 22 records from hauterivian_echinoids_of_the_paris_basin. 144 records from Plasm bearing foraminifera counts of multinet M36/6_MSN1197. 35 records from Abundance, biovolume and biomass of heterotrophic dinoflagellates at station TT012_3-CTD4. 24 records from RNF - Données de la Réserve Naturelle du Marais de Lavours. 75 records from Revision of the Ephippiochthonius complex in the Iberian Peninsula, Balearic Islands and Macaronesia, with proposed changes to the status of the Chthonius subgenera (Pseudoscorpiones, Chthoniidae). 4 records from A new ant species of the Leptogenys sulcinodagroup (Hymenoptera: Formicidae) from Saudi Arabia. 4304 records from TransForest vegetation data. 140 records from Systematics, distribution and biology of the Australian ' micro-flea' wasps, Baeus spp. (Hymenoptera: Scelionidae): parasitoids of spider eggs.. 402 records from Biodiversity of springs and rock seepages 2003. 220 records from Microzooplankton abundance measured on water bottle samples at station PS65/466-2. 18 records from Correction of existing generic and species concepts in Platyceroidini (Coleoptera: Lucanidae: Lucaninae) and the description of four new species of Platyceroides Benesh. 1 records from A new riparian Mantidactylus (Brygoomantis) frog from the Tsaratanana and Manongarivo Massifs in northern Madagascar. 521 records from Schanzenanlage Bergham. 1 records from A new limestone-dwelling leaf-toed gecko (Gekkonidae: Dixonius) from Khao Sam Roi Yot massif, peninsular Thailand. 8 records from Distribution of Quinqueloculina sp. in sediment core 13200-025. 8 records from Crustacean specimens of Kitakyushu Museum of Natural History & Human History. 278 records from Total foraminifera counts of multinet POS231/3_MSN1332. 234 records from Données Phesulma borbonica du Parc national de La Réunion - COBE03. 4484 records from Herbier Louis-Marie (QFA) - Collection de lichens. 47 records from Southern distributional limits of Meliponini bees (Hymenoptera, Apidae) in the Neotropics: taxonomic notes and distribution of Plebeia droryana and P. emerinoides in Argentina. 132 records from Matter enrichment of the macrofauna community of MAC station 13368-008. 129 records from Abundance of dead benthic foraminifera in sediment core CD86_06_BC5. 258310 records from Oiseaux nicheurs de France métropolitaine 2009-2012 - Nidification probable. 273 records from Plasm bearing foraminifera counts from M35/1_MSN1069. 306187 records from Plant. 99 records from Bees of the Hemihalictus series of Lasioglossum Curtis (Hymenoptera, Halictidae) in South Korea. 42 records from Colección de Vertebrados (naturalizados y en fluido) del Departamento de Zoología de la Facultad de Biología de la Universidad de Sevilla. 2 records from Two more new species of Hemiphyllodactylus Bleeker (Squamata: Gekkonidae) from the Shan Hills of eastern Myanmar (Burma). 2 records from A new species of Ledoyerella, L. kunensis sp. nov. (Amphipoda, Senticaudata, Kamakidae) from South West Africa. 3 records from New ants (Hymenoptera: Formicidae) from Micronesia. 3 records from Updated information on genus Gomphidictinus (Odonata: Gomphidae) in China with description of Gomphidictinus tongi sp. nov.. 4 records from A new anchialine species of Naushonia (Decapoda: Gebiidea: Laomediidae) from the Bahamas. 118 records from Schulgelände SGD/Viersen. 774 records from Biodiversidad_ictica_de_la_Isla_Cayo_Serranilla_ExpedicionSeaflower_2017_proyecto_ColombiaBIO. 375 records from Total foraminifera counts of multinet M21/2_MSN650. 505 records from Flora genérica de las gramíneas del estado de Tlaxcala. 49 records from New species of the Eastern Hemisphere genera Afroheriades and Noteriades (Hymenoptera, Megachilidae). 1380 records from Actinomycetes Collection in BCRC. 14 records from Artenerhebung im Wiesenlautersystem/Pfälzerwald. 17014 records from MZFC/Coleccion de Aves. 4 records from A new species of Paraleptophlebia Lestage, 1917 (Ephemeroptera: Leptophlebiidae) and a re-description of adults for Paraleptophlebia westoni Imanishi, 1937 with the first description of the larva, from the Russian Far East. 2883 records from Late Albian Col de Palluel (SE France, Niveau Breistroffer): range chart in percentages of calcareous nannofossils. 53 records from Leopard and Weddell seal program 1999/2002. 444 records from Echinoderms in surface sediments off Sylt collected during HEINCKE cruise HE236. 4309 records from Données naturalistes de Ségolène FAUSTEN. 62 records from Distribución, abundancia y efectos nocivos de tres especies de plantas invasoras. 2 records from Drepanosticta adenani sp. nov., from the Lanjak Entimau Wildlife Sanctuary in Sarawak (Odonata: Zygoptera: Platystictidae). 2 records from Natural History Museum Maastricht (NL) - Herbarium. 172 records from Foraminifera abundance of sediment core MD81-LC07. 5 records from Microplankton abundance in the euphotic zone of the Aegean Sea at Station SEPT-1998-IR64. 1 records from DMNS Egg Collection (Arctos). 449 records from Range table from benthic foraminifers in ODP Hole 181-1119C. 4 records from Microlepidogaster negomata, a new hypoptopomatine catfish (Loricariidae: Hypoptopomatinae) from Rio São Francisco basin, southeastern Brazil. 3656 records from Lepidopterous specimens of Yamagata Prefectural Museum. 662 records from Alterra (NL) - Microarthropods inventory in grassland and arable land. 10428 records from Collection of Coleoptera. 148 records from Lebensraum Fluß/Zwickauer Mulde in Wolkenburg. 2 records from Karpfenteich, Klasse 6d. 8 records from Range table from planktonic foraminifers in ODP Hole 145-883C. 58 records from Review of the genus Prays Hübner, 1825 (Lepidoptera: Praydidae) from China, with descriptions of twelve new species. 557 records from Total foraminifera counts of multinet SO117_MSN1244. 7 records from Taxonomy of Morellia Robineau-Desvoidy (Diptera: Muscidae): revision of the subgenera Morellia s. str. and Parapyrellia Townsend. 5853 records from FloVegSI-FAV - Faunistical database of ZRC SAZU. 35591 records from Canada Maritimes Regional Cetacean Sightings (OBIS Canada). 270 records from Range table from benthic foraminifers in ODP Hole 181-1122C. 863610 records from Florida Keys Reef Visual Census 2014. 15 records from Monitoreo de Murciélagos en la Etapa de Ejecución de las Obras de Ampliación del EPF Floreña, Yopal, Casanare. 172 records from An updated checklist of aquatic plants of Myanmar and Thailand. 48 records from Phytoplankton abundance at station Casma_2003-01-30_2, Casma, Peru. 4 records from Arthropoda Collection of the Seto Marine Biological Laboratory, Kyoto University. 3 records from Two new species of Garreta Janssens, 1940 (Coleoptera: Scarabaeidae: Scarabaeinae) from Southern Africa. 28 records from Additions to Andiorrhinus (Turedrilus) (Rhinodrilidae, Clitellata) from Eastern Amazonia. 368268 records from Queensland Museum provider for OZCAM. 83 records from Range table from planktonic foraminifers in ODP Hole 182-1133C. 207 records from Plasm bearing foraminifera counts of multinet POS247/2_MSN1379. 244 records from (Table 3) Absolute concentrations and raw counts of seven genera of dinoflagellate in ODP Site 170-1039. 158 records from Planktic foraminifera counts at CTD station M39/4_402CTD-55. 1416 records from EDP Baixo Sabor: Herpetology – Baseline Studies [2009]. 1 records from Molche in Ruschwedel. 46 records from Review of the Madagascan Orphninae (Coleoptera: Scarabaeidae) with a revision of the genus Triodontus Westwood. 2 records from Redescription of two species and five new species of Dispio Hartman, 1951 (Spionidae: Polychaeta) from the eastern Pacific Coast and Caribbean Sea, with a review of the genus. 565 records from Colección Zoológica Universidad del Tolima (CZUT) - Arácnidos. 1 records from Redefinition of Denisiella Folsom & Mills, 1938 (Collembola: Sminthurididae) with description of three new species from Brazil. 5 records from Two new records and one new species of the genus Apelaunothrips from China (Thysanoptera: Phlaeothripidae). 3821 records from Records from the NIWA AllSeaBio marine biology database. 18038 records from Análisis de las relaciones entre las diversidades alfa, beta y gamma a distintos niveles de escala espacial: Procesos históricos y ecológicos que intervienen. V Etapa. 288 records from Plasm bearing foraminifera counts of multinet M21/1_MSN620. 556 records from (Appendix) Stable carbon and oxygen isotopes, and Mg/Ca ratios of foraminifera from ODP Hole 154-925A. 1 records from A new Physoschistura from a Salween affluent in western Yunnan (Teleostei: Nemacheilidae). 1876 records from Plecoptera. 124 records from Range table from benthic foraminifers in ODP Hole 146-889B. 4 records from Contributions to the taxonomy, identification, and biogeography of Thaumatogelis Schwarz, 1995 (Hymenoptera: Ichneumonidae). 12 records from New species of Protosticta Selys from Vietnam with a key to the males of the P. curiosa group (Odonata: Platystictidae). 4 records from Three new genera and three new species of Nearctic Lasiopteridi (Diptera: Cecidomyiidae: Cecidomyiinae) from Asteraceae and Caprifoliaceae, and the tribe Rhopalomyiini subsumed under Oligotrophini. 701 records from Données naturalistes d'Arnaud LE NEVÉ. 1595 records from Phytoplankton abundance in surface water in October 1997, Pisco, Peru. 13 records from First records of two flower bug genera from Myanmar (Hemiptera: Heteroptera: Anthocoridae: Anthocorinae: Oriini), with description of a new species of Bilia. 148 records from (Table 8) Distribution of ostracode species in surface sediments of the eastern Laptev Sea. 7054 records from Colección Limnológica Universidad de Antioquia. 292 records from Birdrace-Wannacks_Topti(c)ker-Lübeck. 544 records from Wald am Schloss Wittgenstein Bad Laasphe. 545 records from Museo Provincial de Ciencias Naturales “Dr. Ángel Gallardo”, Rosario, Argentina - Colección Peces (MG-ZV-P). 67196 records from Actualización y enriquecimiento de las bases de datos del proyecto de evaluación y análisis geográfico de la diversidad faunística de Chiapas. 32588 records from University of British Columbia Herbarium (UBC) - Vascular Plant Collection. 764 records from Isle of Wight non-native invasive species. 58 records from Phytoplankton abundance in surface water in 2003, Ancon, Peru. 2 records from Metrocoris sikkimensis sp. nov. (Hemiptera: Heteroptera: Gerridae) from northeastern India, with a key to species of the compar group occurring in India. 581 records from Floristic records in the Moscow and Novgorod regions. 18 records from The Maugean Skate, Zearaja maugeana sp. nov. (Rajiformes: Rajidae) - a micro-endemic, Gondwanan relict from Tasmanian estuaries.. 71 records from Phytoplankton abundance at station Sechin_2003-10-03_2, Casma, Peru. 10 records from A new species of Megatibicen endemic to Mescalero-Monahans shinnery sands (Hemiptera: Auchenorrhyncha: Cicadidae). 210 records from Abundance of macrobenthos organisms in the northern Wadden Sea in 2008. 2 records from Two new species of stargazers of the genus Uranoscopus (Teleostei: Uranoscopidae) from the western Pacific Ocean. 746 records from Données naturalistes de François BRETON. 1632 records from Espèces végetales sur sable roux du fourré de Ranobe, PK 32 Toliara. 18 records from Rare And New For The Fauna Of The Russian Far East Spiders (Aranei). 4 records from A new slipper lobster of the genus Petrarctus Holthuis, 2002 (Crustacea, Decapoda, Scyllaridae) from Southwest coast of India. 20 records from Phytoplankton abundance in the Wadden Sea off List, Sylt, North Sea in 2004. 1 records from A new species of Lepidodactylus (Reptilia: Squamata: Gekkonidae) from the Kei Islands, Maluku, Indonesia. 15095 records from Museu Paraense Emílio Goeldi - Ophidia Collection. 210 records from Large protozoa abundance measured on concentrated water bottle samples at station PS58/108-3. 4 records from Two new species of orb-weaving spiders of the genus Larinia (Araneae, Araneidae) in meridional Brazil. 210 records from (Table 2) Ostracoda abundances in sediment core PS2185-6 (Lomonosov Ridge). 95 records from Kystfuruskoger i Tysnes og Fusa. 798 records from Range table from planktonic foraminifers in ODP Hole 155-938A. 10416 records from (Table T1) Plankontic foraminifera stratigraphy of ODP Site 184-1143. 104 records from Nomenclatural changes in the higher classification of the family Tettigometridae (Hemiptera: Fulgoroidea) with description of a new tribe and new species and a review of the Iranian tettigometrid fauna. 724 records from Centre d'Estudis Avançats de Blanes, Macroinvertebrados Limno. 8 records from Die Bachspezies 2008/2009. 1381 records from Modelación de la distribución geográfica de las Orchidaceae del Soconusco. 55 records from Big and beautiful: the Megaxyela species (Hymenoptera, Xyelidae) of East Asia and North America. 5 records from Results of palynological analysis of Hole 302-M0004C. 6139 records from Lepidoptera specimen database of Japan. 282602 records from DFO Maritimes Research Vessel Trawl Surveys Fish Observations. 4 records from Danio htamanthinus (Teleostei: Cyprinidae), a new species of miniature cyprinid fish from the Chindwin River in Myanmar. 125 records from Nematode genera abundances at the Arctic Håkon Mosby Mud Volcano (HMMV) of sediment core PS64/390-1c. 149 records from Benthic foraminiferal assemblage (Rose Bengal stained) in MUC SC1-K, size fraction >150 µm. 125 records from Range table from planktonic foraminifers in ODP Hole 155-942C. 355 records from Bird specimens of Saitama Museum of Natural History. 1 records from Redescription of Platynaspis flavoguttata (Gorham) (Coleoptera, Coccinellidae) and notes on nomenclature of Platynaspis kapuri Chakraborty & Biswas. 2 records from A new species of Cyrtodactylus (Squamata: Gekkonidae) and the first record of C. otai from Son La Province, Vietnam. 9 records from Two new species of the conger eel genus Bathycongrus (Anguilliformes: Congridae) from Taiwan. 413 records from (Fig. 5) Sea-surface temperature reconstructions of sediment core MD99-2304. 646 records from Mycology collection, Norwegian Forest and Landscape Institute. 434 records from (Table 4) Distribution of Upper Cretaceous agglutinated benthic foraminifers in ODP Hole 129-801A. 6 records from A new species of the genus Euhemicera (Tenebrionidae: Cnodalonini) from South East Asia, with an updated catalogue of all known species. 36 records from Amazoonops, a new genus of goblin spiders (Araneae: Oonopidae) from the Brazilian Amazon. 3 records from Porphyrocrinus daniellalevyae n. sp. (Echinodermata: Crinoidea), a sea lily from the tropical western Atlantic with a unique crown pattern. 1951 records from flower availability 2008 Alb-korrigiert. 5350 records from Relative abundances of benthic foraminifers of sediment core Svanic90_9004. 23 records from Range table from planktonic foraminifers in ODP Hole 144-874B. 16 records from A new species of the genus Bertholdia Schaus, 1896 (Lepidoptera: Erebidae: Arctiinae) from the Neotropical region: Bertholdia zoenia sp. n.. 18 records from Revision of the Australian Union-Jack wolf spiders, genus Tasmanicosa (Araneae, Lycosidae, Lycosinae). 84 records from New distribution data for some charismatic tramp species of Platygastroidea (Hymenoptera). 10 records from A new species of Rhabdops Boulenger, 1893 (Serpentes: Natricinae) from the northern Western Ghats region of India. 239 records from Range table from benthic foraminifers in ODP Hole 161-974B. 102 records from (Table 1) CTD data, mean spring and annual temperatures and salinities from World Ocean Atlas (WOA, 2001), and Mg/Ca data, sampled with a multinet at station 74 and 81 from POSEIDON cruise 334. 30 records from UWIZM Anoles. 282 records from Pat Livermore's Fungus Records 1976 - 2000. 8 records from Three new species of Cladorhiza (Demospongiae, Poecilosclerida, Cladorhizidae) from the Northeast Pacific Ocean. 5 records from New species and new geographical record of Ochrotrichia Mosely 1934 (Trichoptera: Hydroptilidae) from Rio de Janeiro state, Brazil. 418 records from Pollen analysis of sediment profile TR0 from Truennensee. 210 records from Condamine Alliance. 1 records from The genus Acantholyda (Hymenoptera, Pamphiliidae) of Japan: A revised key and a description of the previously unknown female of Acantholyda flaviventris. 6 records from Tobrilus methanus sp. n. and Tripyla posolskii sp. n. (Nematoda, Triplonchida) from Lake Baikal, Russia. 362 records from Inventory of natural and agroforestry stands characterized by Xylopia aethiopica (Dunal) A. Rich. (south-Benin). 1172 records from Inventario taxonómico de los hongos conidales saprobios del parque Yumka' en Villahermosa, Tabasco. 31 records from Proctolaelaps species (Acari: Mesostigmata: Melicharidae) from Egypt, with description of a new species and complementary descriptions of other five species. 10 records from Two new species of Mendozellus Linnavuori (Hemiptera: Cicadellidae: Deltocephalinae: Deltocephalini) with redescription of Mendozellus asunctia Cheng. 11 records from Tardigrada collection of National Museum of Nature and Science. 181 records from Análisis del ictioplancton del ecosistema costero de Celestún, Yucatán, México. 42 records from Riedkanal Bötzingen. 70 records from (Table T10) Calcareous nannofossil stratigraphy of ODP Hole 198-1212A. 16355 records from Diatomeas (Bacillariophyceae) y dinoflageladas (Dinophyceae) planctónicas más frecuentes en el Golfo de California. 2154 records from DBG Physaria bellii Demographic Monitoring. 873512 records from Dragonfly records from the British Dragonfly Society's Dragonfly Recording Network for the period up to 2014. 48 records from Size fractioned abundances and carbon biomasses of heterotrophic protists at station NIOP-B1_276-1. 61 records from Inventario de vertebrados nativos en las islas Guadalupe, San Benito, Natividad, Asunción, San Roque, Isabel, Marietas, Socorro, Banco Chinchorro y Arrecife Alacranes. 1303 records from Leicestershire and Rutland Reptile Records to 2011. 87998 records from SIRFF - FNE Centre-Val de Loire - Données 2016. 81 records from Smear slide analysis on sediment core GeoB4214-1. 348 records from (Fig. 2) Abundance of Globobulimina affinis in sediment core MD95-2040. 128 records from Streuobstwiese. 125 records from Assemblage of total living benthic foraminifera in sediment core SO129_MC-14. 2932 records from Culture Collection of Algae. 534 records from Collection Vermes - ZMB. 130 records from BIRDRACE - The famous Grouse feat. The James. 145241 records from Western Australian Museum provider for OZCAM. 394 records from ABC_Event data recorded on a day trip to Mongolwe and Chikala Hills Forest Reserve, Machinga District. 3599 records from Diversidad vegetal en un gradiente en la Sierra Madre Occidental: flora y vegetación de la Región de San Javier y Yécora, Sonora. 88 records from Mamíferos voladores y no voladores del suroccidente colombiano. 164 records from Rückkehr der Biber in Rheinland-Pfalz - Biber in der Primmerbach. 176 records from Assemblage of living benthic foraminifera in sediment core SO118_MC-51, >125 µm fraction. 470 records from Migratory shorebirds (sandpipers and plovers) in Hokkaido. 2650373 records from Bryophyte data for Great Britain from the British Bryological Society held by BRC: Atlas 2014. 1596 records from (Appendix Table 3) Relative abundances of planktonic foraminiferal species in sediment core MD01-2390. 3811 records from Distribution of planktic foraminifera in surface sediments of the Atlantic Ocean (ATL947). 78 records from Living benthic foraminifera at station M33/1_MC-15 (WAST), size fraction 30-63 µm. 1 records from Phasmatodea Collection - Instituto Nacional de Pesquisas da Amazônia (INPA). 912 records from Phytoplankton abundance in surface water in August 1997, Pisco, Peru. 14 records from Nano and microzooplankton abundance and biomass at station NBP97-01-13-4. 1110 records from Recursos hidrobiológicos de sistemas cársticos en el municipio de El Peñón, Santander - Proyecto Colombia BIO. 5 records from Three new country records from the genus Limnephilus Leach, 1815 (Trichoptera: Limnephilidae) from the Republic of Kosovo. 38 records from Small Cow-wheat distributions for Scotland 1999 to 2005. 164 records from Large protozoa abundance measured on concentrated water bottle samples at station PS58/014-6. 10 records from Cave-inhabiting Neobisiidae (Arachnida: Pseudoscorpiones) from China, with description of four new species of Bisetocreagris Ćurčić. 1 records from A new species of Creagrutus (Characidae: Stevardiinae) from the upper Río Magdalena, Colombia. 22 records from Taxonomic changes of some neotropical species of Arctiini Leach (Lepidoptera: Erebidae: Arctiinae). 66 records from Waldstück am Schullandheim Bad Bederkesa. 15 records from Review of Anasillomos Londt, 1983 with the description of a new species (Insecta : Diptera : Asilidae). 334 records from Aves de la expedición en el páramo de Bijagual, Boyacá - Proyecto Boyacá BIO. 1500 records from M. Gollop Collection. 1796 records from (Table 2) Raw counts of planktonic foraminiferal species and varieties from the sediment surface samples from the South China Sea. 1 records from Données naturalistes d'Olivier DELZONS. 6821 records from Naturalis Biodiversity Center (NL) - Diptera. 36 records from Schulgarten der Gesamtschule Am Heidberg. 83 records from Coccolith counts of multinet SO119_MSN1272. 68 records from (Table 2.2.1.1) Abundance of sympagic meiofauna of sea-ice core IO-11. 2560 records from Museu Paraense Emílio Goeldi - Opiliones Collection. 1622 records from (Table 1) Distribution of planktonic foraminifera from samples spanning the Cretaceous-Tertiary boundary at ODP Hole 207-1259C. 328 records from Schulhof Gymnasium Hürth Bonnstrasse. 170 records from Benthic meiofauna abundance in surface sediment of core PLG93_BCORE1. 140 records from Gewässer des Wartbergparks Stuttgart (bei der Ökostation der VHS Stuttgart). 10 records from Inventur der Natur rund ums NABU-Naturzentrum in Haseldorf. 8 records from Society Islands beach bum black flies (Diptera: Simuliidae). 280 records from BIRDRACE Bon(n)apartemöwen. 1076 records from Composición florística y estructura de una parcela permanente en bosques húmedos tropicales del municipio de Pie de Pepe, Chocó. 62 records from Données de Mammifères marins en Polynésie française issues du South Pacific Whale Research Consortium. 2882 records from Computarización de material complementario en la Colección Regional de Invertebrados del Pacífico mexicano, Instituto de Ciencias del Mar y Limnología, Unidad Académica Mazatlán, UNAM. 37 records from Microzooplankton abundance and biomass at station NBP97-08-29-1. 4 records from The subfamily Cratocentrinae (Hymenoptera: Chalcididae): reappraisal of their morphological characters and review of the West Palaearctic species, with the description of two new species. 1662 records from Benthic foraminifera counts of sediment core PS1852-2. 2854 records from Range table from planktonic foraminifers in ODP Hole 157-953A. 1030 records from Base de datos de fauna batial, abisopelágica y abisal del Golfo de México. 106 records from Assemblage of living benthic foraminifera in sediment core SO118_MC-51, 30-63 µm fraction. 96 records from Abyssal fauna of the UK-1 polymetallic nodule exploration claim, Clarion-Clipperton Zone, central Pacific Ocean: Echinodermata. 10199 records from natagora-earlybirds. 382 records from Systematic revision of the Andean butterfly genus Orophila Staudinger, 1886 (Lepidoptera: Nymphalidae: Biblidinae). 9861 records from Universidad de Murcia, Dpto. Biología Vegetal (Botánica), Murcia: MUB-MUSCI. 22 records from Range table from planktonic foraminifers in ODP Hole 167-1010B. 13240 records from Hormigas del Museo de Entomología de la Universidad del Valle. 26 records from Reptiles Specimens of Akita Prefectural Museum. 3 records from Two new Cyphoderus (Collembola: Paronellidae) of “ tridenticulati ” and “ bidenticulati ” groups from Brazilian Amazon. 2 records from A new leaf-galling Holopothrips (Thysanoptera: Phlaeothripidae) and the structural alterations on Myrcia retorta (Myrtaceae). 316 records from UWIZM Snakes. 44 records from Wildgehege Glauer Tal (Naturpark Nuthe-Nieplitz). 2 records from A new species of Rock Gecko genus Cnemaspis (Squamata: Gekkonidae) from Western Sarawak, Malaysia. 72 records from Taxonomic revision of the Cis-Andean species of Mylossoma Eigenmann & Kennedy, 1903 (Teleostei: Characiformes: Serrasalmidae). 113 records from Electron Micrograph Database - Terrestrial and Limnetic Specimens. 401 records from Planktonic foraminifer occurrences and zonations from IODP Hole 313-M0029A. 12356 records from Mammal records from Britain from the Atlas of Mammals (1993), with some subsequent records. 224058 records from ARABEL - Arachnologia Belgica. 824 records from Heinersdorfer Sumpfwiese. 95 records from The genus Asiagomphus in Vietnam, with descriptions of three new species, and first descriptions of the male of Asiagomphus auricolor (Fraser, 1926) and of the female of Asiagomphus reinhardti Kosterin & Yokoi, 2016 (Odonata: Gomphidae). 21104 records from Biodiversidad de la Sierra Tarahumara. Lepidoptera: Mimallonoidea, Lasiocampoidea, Bombycoidea y Pyraloidea. 17568 records from Arctic Species Trend Index (ASTI) : Marine. 153 records from Assemblage of total living benthic foraminifera in sediment core SO129_MC-03. 1 records from A new species of the genus Megophrys (Anura: Megophryidae) from Yunnan Province, China. 23317 records from Wolli Creek Preservation Society Bird Survey. 5 records from Description and molecular phylogeny of Axinella nayaritensis n. sp. (Porifera: Axinellida) from East Pacific and remarks about the polyphyly of the genus Axinella. 750 records from Lillachtal mit Kalktuffquelle bei Weißenohe. 62 records from Lepidurus arcticus survey Northeast Greenland 2013. 2807 records from Natura 2000 Vallée de la Seille. 10894 records from Occurrences of the invasive plant species Heracleum sosnowskyi Manden. in the Komi Republic territory (European North-East Russia). 257 records from Phytoplankton long-term time-series at the fixed coastal station in the Gulf of Naples, data for the years 1984-1991. Part 2. 562 records from Inventario de Hymenóptera; parasítica en México. 306 records from VSN-Wiese. 640 records from (Appendix G) Benthic foraminifera extinction group species in ODP Hole 167-1012B. 6 records from Taxonomic studies of Japanese Formicidae part 3: genus Vollenhovia.. 1 records from Additions to the list of Finnish Bibionomorpha (Diptera, Nematocera). 63085 records from Alien plant presence dataset from the point-radius plot surveys in 2010-2015 in Taiwan. 7 records from Microplankton counts and carbon biomass at station TT011_8-CTD96. 17032 records from Colección de insectos agrícolas del proyecto diversidad en sistemas de cultivos. 10527 records from Ibaraki Nature Museum, Fungi collection. 2 records from A new species of Liriomyza Mik (Diptera, Agromyzidae) on okra in Brazil. 10186 records from Colección de Reptiles - Museo de Herpetología de la Universidad de Antioquia. 372 records from Relative abundance of ostracods in sediment core Sv09. 814 records from Chironomid Specimen records in the Chironomid DNA Barcode Database.. 1327 records from Museu Valencià d′Història Natural - Fundación Entomológica Torres Sala: FETS. 209 records from Large protozoa abundance measured on concentrated water bottle samples at station PS58/009-6. 342810 records from Amis_des_Marais_du_Vigueirat_2017_12_18. 17 records from Assemblage of living benthic foraminifera in sediment core SO119_MC501, >125 µm fraction. 40 records from A new species of long-legged terrestrial Terrapotamon Ng, 1986 (Crustacea: Brachyura: Potamidae) from limestone formations in Satun, southern Thailand. 48 records from Atelier Malacologie continentale, 14-15septembre, La Flèche (Sarthe). CEN Pays de la Loire. 152 records from BIRDRACE Nachtigallen. 1 records from Zoological Museum Amsterdam, University of Amsterdam (NL) - Bryozoa. 61 records from Données de Midi-Pyrénées transmises par Pascal Peyrache.. 1286 records from ConDidact Citizen Science Surveys - Amphibians 2007. 10 records from Three new species of Leptanilloides Mann from Andean Ecuador (Formicidae: Leptanilloidinae).. 148 records from Total foraminifera counts of multinet FCA97C_MSN1345. 2 records from Biodiversidad del orden Araneae (Arachnida) de las Islas del Golfo de California, México. 96 records from Données naturalistes (Rhopalocères et Zygènes) de Jude LOCK (indépendant). 129 records from SNH Invertebrate Site Condition Monitoring 2013/14: Glenmore Forest SSSI. 323 records from Size of planktic foraminifera at CTD station PS55/083-1. 122 records from Taxonomy and molecular phylogeny of the Platystictidae of Sri Lanka (Insecta: Odonata). 637 records from Phytoplankton abundance measured on water bottle samples at station PS65/514-2. 221 records from (Table II) Abundance of epibenthic phyla and classes during RSS James Clark Ross cruise JR144. 50 records from Estacion Biologica Donana - CSIC, Anfibios (EBD_HERP). 3 records from Diversity of Sternaspidae (Annelida: Terebellida) in the South China Sea, with descriptions of four new species. 14 records from New species, new records and updated subgeneric key of Bactrocera Macquart (Diptera: Tephritidae: Dacinae: Dacini) from India. 397 records from University of Amsterdam (NL) - Páramo Vegetation Research, National Natural Park El Cocuy, Colombia. 240 records from Total foraminifera counts of multinet M21/4_MSN704. 40832 records from Zomerganzen - Summering geese management and population counts in Flanders, Belgium. 294 records from Abundance of broken diatom frustules measured on water bottle samples at station PS58/088-4. 717 records from Redland City Council Citizen Science Portal. 15 records from Hessen-GEO-Tag am Schlossberg von Homberg/Efze. 36810 records from Insect collection of Biodiversity Center of Japan, Ministry of the Environment. 478 records from Caracterización de algas y comunidad íctica de la Isla Cayo Serrana durante la Expedición Seaflower 2016 - Proyecto Colombia BIO. 8 records from New species, new records, and new collection data of Rhyacophila from China (Trichoptera: Rhyacophilidae). 307 records from HBRG Invasive Non-native Plants Dataset. 79884 records from North East Scotland Terrestrial Mammals 1900-2017 (excluding squirrels, wild cats and marine mammals). 6 records from Pushing the limits - two new species of Pteromalus (Hymenoptera, Chalcidoidea, Pteromalidae) from Central Europe with remarkable morphology. 332 records from Steinbruch Mainz-Weisenau, 3. Jahr. 3000 records from Museu Paraense Emílio Goeldi - Carcinológica Collection. 3251 records from Inventario florístico de la Sierra de Huautla, Morelos. 717 records from Inventario de sanguijuelas (Annelida: Clitellata Hirudinea) de México, con énfasis en las especies del centro de México. 240 records from BIRDRACE The early birds. 33694 records from UMMZ Herpetology Collection. 229 records from Queen Charlotte Sound / Tōtaranui and Tory Channel / Kura Te Au (HS51) Hydrographic Survey Marine Mammal Observations. 2358 records from RECORD Orthoptera Data. 6 records from Two new species of Guyruita Guadanucci et al., 2007 (Araneae, Theraphosidae) from Brazil. 3 records from New species of Graphocaecilius Enderlein (Psocodea: ‘ Psocoptera’: Lachesillidae) from Colombia. 541 records from Abundance of Polychaeta species in surface sediments of the east Greenland continental slope (75° N section). 4 records from A new species of Polyipnus (Stomiiformes: Sternoptychidae) from the Western South Pacific. 2 records from A beautiful new yellow salamander, genus Bolitoglossa (Caudata: Plethodontidae), from the northeastern slopes of the Cordillera de Talamanca, Costa Rica. 2496 records from Birds Specimens. 7124 records from Plant Specimen from Herbarium (HIB) in China, Wuhan Botanical Garden, Chinese Academy of Sciences. 90 records from Schulgelände Kranich-Gymnasium (Salzgitter). 6 records from Contributions to the study of Idiocerinae (Homoptera: Auchenorrhyncha: Cicadellidae) of Central Asia with notes on synonymy. 2 records from A revision of the Anthaxia (Anthaxia) midas Kiesenwetter, 1857 species-group (Coleoptera: Buprestidae: Anthaxiini). 1722 records from Herpetofauna de la región marina prioritaria Corredor Puerto Madero, Chiapas, México. 120 records from ISM Ichthyology Collection. 11870 records from Upper Silesian Museum, Bird Observations. 86 records from Fliegenhaupt Marksuhl. 31 records from Type specimens of invertebrate collection at University of Oulu Zoological Museum. 11892 records from DMNS Mammal Collection (Arctos). 1588 records from Données naturalistes de Quentin ROME. 4398 records from Back from the Brink vascular plant species abundance and distribution for Great Britain for the period 2002-2009. 1645 records from (Appendix Table 2) Raw counts of planktonic foraminiferal species from sediment core MD01-2390. 1 records from A new species of the genus Pachytriton (Caudata: Salamandridae) from Hunan and Guangxi, southeastern China. 267 records from Range table from benthic foraminifers in ODP Hole 171-1050A. 107 records from SEWBReC Springtails and allies (South East Wales). 226 records from (Table 2) Stable oxygen and carbon data, and relative abundances of selected planktonic foraminiferal species in the surface sediment samples retrieved during the SO-189 cruise off W Sumatra. 1 records from Culicoides Latreille biting midges (Diptera: Ceratopogonidae) of the Dongzhaigang mangrove forest, Hainan Province, China. 75 records from Taxonomic review of the ladybird genus Sticholotis from China (Coleoptera: Coccinellidae). 108 records from Benthic foraminifera abundance in ODP Leg 155 holes. 1053 records from IBF Monitoring of Fungi. 140560 records from The Himalayan Uplands Plant database (HUP Version 1). 262 records from Artenvielfalt auf dem Schulgelände. 8 records from A new species of Decomia Poppius from Laos and Thailand, with an annotated checklist and keys to genera and species of tribe Decomiini from Indochina (Hemiptera: Heteroptera: Miridae: Phylinae). 2702 records from (Table 3) Distribution of planktonic foraminifera in the early Cretaceous and early Eocene to late Oligocene sections of ODP Hole 149-897C. 107 records from Macrofauna abundance in surface sediment sampled during cruise DI237. 119 records from Programme de valorisation des zones humides chassées - volet Amphibiens. 21541 records from National Museum of Natural Science. 3018 records from Caracterización de flora, edafofauna epígea, anfibios y aves del Complejo de Páramos Pisba, Boyacá. 50 records from Eupithecia gypsophilata, a new species in the graphata species group of the genus Eupithecia Curtis (Lepidoptera, Geometridae, Larentiinae). 10 records from Distribution and habitat of the Laotian Rock Rat Laonastes aenigmamus Jenkins, Kilpatrick, Robinson & Timmins, 2005 (Rodentia: Diatomyidae) in Vietnam. 238 records from Large protozoan and small metazoan abundance measured on concentrated water bottle samples at station PS65/593-18. 55 records from Catalog of the Paramacronychiinae of China (Diptera: Sarcophagidae). 15453 records from Données de la collection d'ichtyologie du MNHN (GICIM). 3 records from A new species of Ascidiacea (Herdmania andamanensis sp. nov.) from Andaman and Nicobar Islands, India. 138 records from BIRDRACE Pfeifenten. 53 records from Données 2017 de l'Observatoire de la Biodiversité des Forêts. 1 records from Enneophyllus ecarina, a new species of scaphopod shell dwelling hermit crab (Crustacea: Decapoda: Anomura: Paguridae) from deep-sea off the Ryukyu Islands, southern Japan. 15 records from Ephemeroptera Collection - Instituto Nacional de Pesquisas da Amazônia (INPA). 480 records from Knechtweide (Kohlfurth). 40 records from Collections ichtyologiques et herpétologiques (BOUM). 41 records from Benthic macrofauna abundance of sediment core 12930-073. 4 records from Description of Rhamma dawkinsi (Lepidoptera: Lycaenidae) a new mountain butterfly from Colombia. 21633 records from Données naturalistes de Bruno OGER. 5467 records from Colección de mariposas del Museo de Entomología de la Universidad del Valle. 9 records from Ta xonomic study on the Chinese Steninae (Coleoptera, Staphylinidae), with descriptions of three new species of the Genus Stenus Latreille. 42 records from Revision Of The Spider Genus Neoanagraphis (Araneae, Liocranidae). 10 records from Meniscus Midges (Dixidae) of Ireland. 8 records from A new species of poison-dart frog (Anura: Dendrobatidae) from Manu province, Amazon region of southeastern Peru, with notes on its natural history, bioacoustics, phylogenetics, and recommended conservation status. 570 records from Loup 2014 présence occasionnelle communale (réseau Loup-Lynx ONCFS). 706 records from Données naturalistes de Hubert GUIMIER. 1854 records from Données naturalistes de Hervé BOUYON. 1472 records from Collection rousset -1947-2013. 2 records from The Shiny Cowbird, Molothrus bonariensis (Gmelin, 1789) (Aves: Icteridae), at 2,800 m asl in Quito, Ecuador. 20 records from Ten new species of the spider genus Pholcus Walckenaer, 1805 (Araneae, Pholcidae) from Southeast Asia. 2 records from Austromorium, a new myrmicine ant genus from Australia (Hymenoptera: Formicidae).. 507 records from Plasm bearing foraminifera counts from M35/1_MSN1048. 163 records from Dinoflagellate cysts of ODP Hole 189-1172D. 57 records from CSIRO Yellow Box Fragmentation Project. 256 records from Review of some species groups of the genus Oospila Warren, with descriptions of nine new species (Lepidoptera: Geometridae: Geometrinae). 11841 records from Entomology Collection at the Natural History Museum of Utah. 327 records from Total foraminifera counts of multinet M21/2_MSN629. 3 records from On Plesionika persica (Kemp, 1925) and P. reflexa Chace, 1985 (Crustacea: Decapoda: Pandalidae) from India. 99877 records from ALCB - Herbário Alexandre Leal Costa. 228 records from BIRDRACE LiLaLau. 450 records from Total foraminifera counts of multinet POS247/2_MSN1372. 9446 records from Biobanco de ADN Vegetal de la Universidad de Salamanca: SALA-DNA. 8 records from Forest Spiders of South East Asia With a revision of the sac and ground spiders (Araneae: Clubionidae, Corinnidae, Liocranidae, Gnaphosidae, Prodidomidae and Trochanterriidae).. 77135 records from Fish specimens of Kagoshima University Museum. 78 records from (Table T8) Occurrence of Neogloboquadrina pachyderma in ODP Hole 178-1098C. 1820 records from UTEP Invertebrates (Arctos). 140 records from Diptera Collection of Museum and Institute of Zoology PAS. 214 records from Pseudoscorpiones Collection - Instituto Nacional de Pesquisas da Amazônia (INPA). 98 records from Schulteich Freie Waldorfschule Darmstadt. 6 records from Description of a new species of Euptychiina (Lepidoptera: Nymphalidae: Satyrinae) from South America. 24 records from A new genus of ground and litter-dwelling pholcine spiders from Sarawak (Araneae, Pholcidae). 18108 records from Highland bird data 2002 - 2003 - non-breeding records. 44 records from Electrogena brulini sp. nov. and E. vipavensis Zurwerra & Tomka, 1986 syn. nov. revealed by integrative taxonomy of E. gridellii (Grandi, 1953) (Ephemeroptera: Heptageniidae). 2 records from A new species of Pegylis Erichson, 1847 (Coleoptera: Scarabaeidae: Melolonthinae: Pegylini) from Ethiopia. 464 records from Relative abundance of coccosphere-units at site GIK23414. 584 records from Monitoreo y recolección de la diversidad de razas de maíz criollo en la región de la Huasteca en México para complementar las colecciones de los Bancos de germoplasma de INIFAP y CIMMYT. 293 records from Total foraminifera counts from M35/1_MSN1061. 56 records from Herbario MAIA, colección Flora Forestal del INIA-CIFOR. 264 records from Plasm bearing foraminifera counts of multinet M21/2_MSN627. 47286 records from CNIN/Abejas de México/Apoidea. 4158 records from RNF - Données du Parc Naturel Régional du Vercors. 3731 records from (Table 2) Distribution of planktic foraminifers of sediment core D11957P. 45 records from Crustacea specimens of Kuroshio Biological Research Foundation. 641 records from Flora útil del Municipio de la Huerta, Jalisco. 328 records from Insectes Hyménoptères Scollidés de France. 119 records from Range table from planktonic foraminifers in ODP Hole 146-892A. 1452 records from Phytoplankton abundance during Gunnar Thorson cruise GT90/5. 1618 records from Diversité et distribution de quelques espèces de plantes agroforestières au Bénin. 736 records from Inventario y monitoreo del Canal de Infiernillo para el comanejo de los recursos marinos en el territorio Seri, Golfo de California. 477 records from Total foraminifera counts of multinet M36/6_MSN1196. 1 records from First description of the male of the type species Meotipa picturata Simon, 1895 and description of a new Meotipa species (Araneae, Theridiidae) from India. 4717 records from Weddell Sea macrozoobenthos EASIZ I. 3739 records from Distribution of planktic foraminifera in sediment core GIK23415-9. 277 records from IOW Natural History & Archaeological Society Marine Records. 30 records from A new species of Leptolalax (Anura: Megophryidae) from northern Vietnam. 2187 records from Modelos predictivos de distribución geográfica para Spizella wortheni, Cynomys mexicanus, Vulpes macrotis zinseri y Taxidea taxus berlandieri. 18 records from Records of pine martens from SNH casework reports and licence applications, 2005 - 2016. 39 records from Ostracod species in Oligocene sediments of core CRP-3. 6097 records from Fauna y flora en áreas con cultivos de palma de aceite en el norte y oriente de Colombia. 50 records from Cyanobacteria, phototrophic and heterotrophic pico-nanoplankton at station TT007_10-CTD124. 2528 records from Communauté_de_communes_Asse_Bléone_Verdon_2017_12_18. 723 records from Phytoplankton abundance measured on water bottle samples at station PS65/545-1. 291 records from Abundance of broken diatom frustules measured on water bottle samples at station PS58/092-3. 24 records from Art´n Vielfalt im Kinderwald. 270 records from Waldi-Weiher. 5326 records from Specimens of cyanoprocaryotes herbarium KPABG. 5548 records from (Table 5) Eocene to Oligocene nannofossil range chart for ODP Hole 134-829A. 432 records from (Table 1) Distribution of foraminifera in the Miocene section of ODP Hole 133-815A. 234224 records from Phase 2 Lowland Grassland Survey of Wales. 677 records from Invasive Non-Native Species, Outer Hebrides. 38 records from Benthic macrofauna abundance of sediment core 13077-093. 940 records from Gewann Krampf (Heilbronn). 5673 records from Naturalis Biodiversity Center (NL) - Crustacea. 3 records from On new or poorly known Australian Filistatidae spiders (Araneae: Araneomorphae), including a study on the fine morphology of Wandella. 148 records from Naturschutzgebiet Lippeaue (Marl) - Pfadis in Sickingmühle. 464 records from Filogenia de las cactáceas columnares (Pachycereeae) con base en caracteres anatómico-morfológicos. 467 records from Danish Ants (Formicidae). 41 records from Benthic macrofauna abundance of sediment core 13201-002. 74 records from Polychaeta abundance in surface sediments of the east Greenland continental slope (79° N section). 1575 records from Catálogo taxonómico y biogeográfico de los radiolarios (orden Polycystina) de la región central y sur del Golfo de California. 607 records from Inventory of Bassila forest (North-Benin). 30 records from Abundance, biovolume and biomass of heterotrophic dinoflagellates at station TT007_1-CTD8. 336 records from (Table 2) Abundance of ostracods in surface sediment samples from the Admiralty Bay, King George Island, West Antarctica. 144 records from Phytoplankton abundance measured on water bottle samples during Jan Mayen cruise JM2. 157 records from (Table 2) Relative abundances of shallow-water foraminifera in ODP Hole 133-821A. 3562 records from Georgia Southern University - Savannah Science Museum Herpetology Collection. 2518342 records from Données issues de Clicnat (Base de données naturaliste picarde gérée par Picardie Nature). 651 records from Molluscs in surface sediments off Sylt collected during HEINCKE cruise HE293. 7 records from Revision of Terellia amberboae group of species (Diptera: Tephritidae). 840 records from DATABASE OF FINDS OF RARE LICHEN SPECIES Lobaria pulmonaria IN RUSSIA. 8 records from Microplankton abundance in the euphotic zone of the Cretan Sea at Station JULY-1994-D2. 13275 records from (Appendix 8) Distribution of barnacles, bivalves, gastropods, and calcified worm tubes in sediment samples collected between 1995 and 2010 in the San Francisco Bay coastal system. 6 records from Hemichordata collection of National Museum of Nature and Science. 742 records from Composición y estructura de la ornitofauna de la reserva de la biósfera Pantanos de Centla. 156 records from SNH Invertebrate Site Condition Monitoring 2013/14: Earlshall Muir SSSI. 5 records from A New Southern Caribbean Species of Angel Shark (Chondrichthyes, Squaliformes, Squatinidae), Including Phylogeny and Tempo of Diversification of American Species. 28 records from Nano and microzooplankton abundance and biomass at station NBP97-01-01-10. 31 records from Macrohongos de los bosques montanos del Oriente Antioqueño, Cañón del río Melcocho, en el municipio de El Carmen de Viboral, Antioquia - Proyecto Colombia BIO. 157 records from Planktic foraminifera counts at CTD station PS55/078-1. 8 records from Determinación de la clase Reptilia presente en el corregimiento de Juanchaco, Valle del Cauca, Colombia para el mes de Septiembre de 2017. 451 records from (Table 2) Species density and composition of an inshore and offshore station in Kongsfjord, Svalbard. 31 records from Assemblage of living benthic foraminifera in sediment core SO118_MC-02, 30-63 µm fraction. 1245 records from Distribution of nanoplankton at trap WR2. 158 records from Birdrace-Bielefinken-Bielefeld. 13624 records from Ecosphère_2017_12_18. 227 records from Müritz-Nationalpark. 125 records from Range table from ostracoda in ODP Hole 143-866B. 65 records from (Table 2.2.1.1) Abundance of sympagic meiofauna of sea-ice core IO-2. 47652 records from R. L. McGregor Herbarium Lichen Collection. 1320 records from Peces pelágicos de la Isla Cayo Serrana durante la Expedición Seaflower 2016 - Proyecto Colombia BIO. 70786 records from Entomological Specimens of Museum of Nature and Human Activities, Hyogo Pref., Japan. 94 records from Distribución de la Nutria (Lontra longicaudis) en la cuenca baja del río Sinú en el departamento de Córdoba. 156 records from Birds Specimens of Akita Prefectural Museum. 1474 records from Coleção de Bryozoa do Museu Nacional - UFRJ. 4541 records from UAM Fish Collection (Arctos). 5 records from Certain species of Plecoptera from the headwater springs of National Integration River (São Francisco), Brazil. 1 records from A new species in the troglomorphic scorpion genus Troglotayosicus from Colombia, representing the northernmost known record for the genus (Scorpiones, Troglotayosicidae). 143 records from Isotope tracer experiment: meiofauna counts. 19 records from Données naturalistes de LE GLOANEC Vincent. 444 records from MSUM Ichthyology and Herpetology Collections. 14 records from Microplankton abundance at Station SEPT-1997-GN36199704606MNB01 in the euphotic zone of the Aegean Sea in September 1997. Part 3 - coccolithophores and other groups. 370 records from Size of planktic foraminifera at CTD station PS55/051. 1474 records from Phytoplankton abundance in surface water in January 1996, Paita, Peru. 154 records from Corn bunting breeding distribution in Scotland. 497 records from Banco de Germoplasma de la Universidad Rey Juan Carlos. 38 records from Benthic macrofauna abundance of sediment core 13200-008. 1929 records from Coleção Zoológica de Referência da Universidade Federal de Mato Grosso do Sul - Reptilia (ZUFMS-REP). 176 records from Foraminifera species abundances from tow TT007_7-MOC13. 672 records from KARSTLANDSCHAFT SÜDHARZ - VOM GIPSABBAU BEDROHT (Grenzstreifen am Röseberg). 15 records from New data on the Pterophoridae fauna of Liberia (Lepidoptera: Pterophoridae). 1 records from On the genus Paleonura (Collembola: Neanuridae: Neanurinae) from the Americas and description of a new species from Puerto Rico. 127 records from Assemblage of living benthic foraminifera in sediment core GeoB3604-1. 58950 records from River Biologists' Database (EPA). 49804 records from CABI Africa Invasive and Alien Species data. 9200 records from Eurobodalla Regional Botanic Gardens. 306 records from Selztal bei Friesenheim. 9 records from New species of the subfamily Braconinae (Hymenoptera: Braconidae) from the Russian Far East. 3567 records from UCM Mammal Collection (Arctos). 66 records from Microzooplankton abundance and biomass at station TT045_19-3. 57685 records from Tiroler Landesmuseum Ferdinandeum. 29 records from The bees of the genus Colletes Latreille (Hymenoptera: Colletidae) of the Caucasus region. 142 records from Phytoplankton abundance at station Rigel_1_2005-02 in Febraury 2005, Chipana, Chile. 190 records from Anfibios y reptiles de sistemas cársticos en el municipio de El Peñón, Santander - Proyecto Colombia BIO. 1161 records from (Figure 4) Distribution chart of benthic foraminifers in ODP Site 126-791. 12 records from A new widespread European bee species of the genus Dasypoda Latreille (Hymenoptera, Apoidea). 135732 records from Natural History Museum, Vienna - Herbarium W. 208 records from BIRDRACE Die Vriesischen Feigen-Vögel (VFV). 7834 records from Weddell Seal census, Vestfold Hills, Antarctica. 66 records from Phytoplankton abundance measured in surface water during VALDIVIA cruise VA137. 16832 records from Odonata records from RSPB Reserves 1970-2009. 1038 records from Données supplémentaires Atlas des Mammifères marins. 2681 records from DREAL_PACA_-_N2000_-_Parc_Naturel_Régional_du_Verdon_2017_12_18. 9 records from Leptobasis linda sp. nov. from Ecuador (Odonata: Coenagrionidae). 273 records from Plasm bearing foraminifera counts from multinet SO119_MSN1295. 130 records from Abundance of dead benthic foraminifera in sediment core CD86_02_BC5. 29 records from Mesostigmatic mites (Acari: Mesostigmata) of Saudi Arabia (excluding Phytoseioidea), new records and a key to the known species. 1680764 records from NBIS Records to December 2016. 290 records from Abundance of radiolaria at station UT99-23-2. 545 records from Rohrmeistereiplateau und angrenzendes Gebiet. 1426 records from SPC PROCFish/C Invertebrates Observations Kiribati 2004. 53 records from Assemblage of total living benthic foraminifera in sediment core SO117_MC468. 66 records from (Table 1.2.1.1) Abundance of sympagic meiofauna of sea-ice core PS69/574-1. 1749 records from Floral visits on plants, InsectScale 2008. 5272 records from Survey and monitoring records for Scottish Wildlife Trust reserves from reserve convenors and Trust volunteers - Unassessed data. 3551 records from Planktic foraminifera abundance in counts of Hole PRAD1-2. 48 records from Range table from planktonic foraminifers in ODP Hole 178-1096A. 706 records from South American Antarctic Marine Biodiversity Literature. 2 records from New record for the deep-sea genus Tripoplax (Mollusca: Polyplacophora) in the eastern Pacific. 103 records from Métropole_Nice_Côte_d'Azur_2017_12_18. 5 records from A new species of Laccobius Erichson and additional faunistic records of the genus from China, with a key to subgenus Glyptolaccobius Gentili (Coleoptera: Hydrophilidae). 1934 records from Stoneworts in Wales. 2 records from Recognition of a new species of Carmenta from New Mexico supported by morphology and mitochondrial cytochrome oxidase I data (Lepidoptera: Sesiidae: Sesiinae: Synanthedonini). 108 records from City of Edinburgh Natural Heritage Service - Large Red Damselfly Survey. 170 records from Frohlinder Mühlenbach (Dortmund-Kirchlinde). 3796 records from Fungi Collection. 10 records from Two new species of tribe Agalliini (Hemiptera: Cicadellidae: Megophthalminae) with note on intraspecific variations. 960 records from Range table from planktonic foraminifers in ODP Hole 144-873B. 51 records from Abundance of living benthic foraminifera in sediment core CD86_06_BC5. 308 records from Naturmiljø Bergensbanen 2015 (project number 616033). 21 records from Thirteen new records of ferns from Brazil. 46 records from Meiofauna abundance in sediment core 54301-010. 334 records from Modelación de la distribución y abundancia de las subespecies de venado cola blanca en México: implicaciones de conservación y manejo. 31229 records from The reptiles and amphibians collection (RA) of the Muséum national d'Histoire Naturelle (MNHN - Paris). 12028 records from globec/soglobec/process/krill. 9 records from Four subgenera of Bracon Fabricius (Hymenoptera, Braconidae, Braconinae) newly recorded from China, with description of five new species. 384 records from Steinbruch Mainz-Weisenau, 2. Jahr. 12455 records from LSU Shirley C. Tucker Herbarium at Louisiana State University - Lichens. 14708 records from NE Scotland other invertebrate records 1800-2010. 540 records from Plasm bearing foraminifera counts from multinet SO119_MSN1281. 2 records from Hieracium attenboroughianum (Asteraceae), a new species of hawkweed. 8 records from A new remarkable and Critically Endangered species of Astyanax Baird & Girard (Characiformes: Characidae) from Chapada Diamantina, Bahia, Brazil, with a discussion on durophagy in the Characiformes. 1139 records from Colección Ornitológica de la Universidad del Valle. 5978 records from (Table T1) Calcareous nannofossil stratigraphy of ODP Site 198-1213. 15774 records from Inventario florístico de la región Calakmul-parte baja de la región Lacandona (Cuenca alta del Usumacinta y Marqués de Comillas). 5538 records from (Table 2) Distribution of Miocene planktonic foraminifers in sediments of ODP Hole 138-844B. 258 records from Total foraminifera counts from M35/1_MSN1065. 1520 records from Marine Turtles. 293 records from An Online Database of the Immatures of Coleoptera (Arthopoda, Insecta) Described from Brazil. 207 records from Données de Mammifères marins. Mission AGOA de 2012 à 2014. 49 records from Colección de Aráceas del Jardín Botánico San Jorge. 1704 records from Waarneming.nl (NL) - Great Grey Shrike Count 2009-2010. 9 records from Distribution of Quinqueloculina sp. in sediment core 13200-017. 2962 records from Alterra (NL) - Microarthropods inventory in calcareous grasslands. 375 records from Total foraminifera counts of multinet M21/2_MSN650. 16 records from Hemibates koningsi spec. nov: a new deep-water cichlid (Teleostei: Cichlidae) from Lake Tanganyika. 1 records from Contributions to the taxonomy of Minixi Giordani Soika and Alphamenes Van der Vecht (Hymenoptera, Vespidae, Eumeninae), with an identification key to the species of the latter. 38 records from The Goblin spider genus Xestaspis in Sri Lanka (Araneae: Oonopidae). 38 records from Revision of the genus Shairella Chûjô, 1962 (Coleoptera: Chrysomelidae: Galerucinae) from Taiwan, with descriptions of five new species. 17 records from Microzooplankton abundance and biomass at station NBP97-03-03-5. 2 records from Deep-sea ascidians from Papua New Guinea. 3 records from First description of the male of the eyeless spider Draconarius tortus Chen, Zhu & Kim 2008 from China (Araneae: Agelenidae: Coelotinae). 44 records from Revision of the Neotropical genus Macreupelmus Ashmead (Hymenoptera: Chalcidoidea: Eupelmidae). 1199 records from Inventario y catálogo de ostrácodos recientes de los mares mexicanos. 529 records from Total foraminifera counts from multinet M31/3_MSN915. 796082 records from NatureServe Network Species Occurrence Data. 42256 records from Tagged Seal Location Data from SOGLOBEC. 2 records from Revision of the Australian Wet Tropics endemic rainbowfish genus Cairnsichthys (Atheriniformes: Melanotaeniidae), with description of a new species. 333 records from Données naturalistes de Renaud PUISSAUVE. 621112 records from Dry Tortugas Reef Visual Census 2010. 1764 records from Universidad de Murcia, Dpto. Biología Vegetal (Botánica), Murcia: MUB-HEPATICAE. 5 records from Nomenclatural changes in Mymaridae (Hymenoptera: Chalcidoidea). 839 records from Pollen analysis of sediment profile HAE10 from Hämelsee. 2 records from Discovery of the Dinoponera lucida male (Hymenoptera, Formicidae), a threatened giant ant from the Atlantic rain forest. 182 records from Re-examination of the reef corals of Cocos (Keeling) Atoll, Charlie Veron. 26770 records from Instituto Pirenaico de Ecología-CSIC: Herbarium JACA. 202 records from Naturgrundstück (Eutin). 10 records from A new pelvic-less species of Melanorivulus Costa (Cyprinodontiformes: Cynolebiidae), with a discussion on the pelvic-fin absence in killifishes. 1 records from Description of a new Penaeidae (Decapoda: Dendrobranchiata) species, Farfantepenaeus isabelae sp. nov.. 97280 records from Norwegian Lepidoptera working group. 20 records from Five new species and novel descriptions of opposed sexes of four species of the spider genus Attacobius (Araneae: Corinnidae). 279 records from Large protozoan and small metazoan abundance measured on concentrated water bottle samples at station PS65/591-11. 2 records from A new deep-sea species of the caridean genus Bresilia Calman, 1896 (Crustacea: Decapoda: Bresiliidae) from Sagami Bay, central Japan. 776 records from Pteridophyta collection of Museum of Natural and Environmental History, Shizuoka. 385 records from (Table 2d) Nannofossil distribution chart of petroleum well Great-Eastern-1. 12282 records from NE Scotland fish records 1800-2010. 224 records from Natura 2000 PnrL. 22056 records from Census of the species of Benin. Data mobilized in the framework of JRS Benin project and funded by JRS Biodiversity Foundation. 161 records from Matter enrichment of the macrofauna community of MAC station 13077-001. 696 records from Range table from planktonic foraminifers in ODP Hole 155-930B. 4 records from Moriphila furva gen. and sp. nov. (Hemiptera: Psylloidea: Homotomidae), a new jumping plant-louse from Korea associated with Morus australis (Moraceae). 2 records from Aradidae from Vietnam V. Bifurcatoaptera, a new genus of apterous Carventinae (Hemiptera: Heteroptera: Aradidae) from Vietnam. 5 records from The genus Zelurus Hahn, 1826, in Brazilian caves: description of new species and comments on the potential distribution of the genus in South America. 497 records from PSU-Seagrass Collection. 270 records from Foraminifera species abundances from tow TT011_7-MOC66. 56667 records from Vascular plants of south-central China. 378 records from Entomological collection of the National Museum. 246 records from BIRDRACE Punkbirder Helgoland. 415 records from Abundance of empty diatom frustules measured on water bottle samples at station PS58/041-2. 12 records from Sächsische Schweiz (Pfaffenstein). 578 records from Conservación de la tortuga caguama del Pacífico (Caretta caretta): protección dentro del hábitat crítico de alimentación y desarrollo en Baja California Sur. 11960 records from Données ONEMA BDMAP 2014. 1108 records from Inventario de gasterópodos terrestres y dulceacuícolas del área focal de Ixcan, Chiapas. 6 records from Revision of Tomocerus similis Chen & Ma, with discussion of the kinoshitai complex and the distal tibiotarsal chaetae in Tomocerinae (Collembola, Tomoceridae). 34107 records from Field Museum of Natural History (Zoology) Amphibian and Reptile Collection. 2 records from Living Cirripedia. 27 records from Review of the genus Amemboides Polhemus & Andersen, 1984 (Hemiptera: Heteroptera: Gerridae) from China, with description of a new species. 1568 records from Helmintos parásitos de peces del sureste de México. 1464 records from Benthic foraminiferal number, diversity, and species abundance of size fraction >125µm across sapropel S5 in core M40/4_67SL from the lower bathyal of the western Levantine Basin. 2 records from Cnemaspis rajakarunai sp. nov., a rock dwelling day-gecko (Sauria: Gekkonidae: Cnemaspis) from Salgala, an unprotected lowland rainforest in Sri Lanka. 61 records from Naturpark Kottenforst-Ville 15.6.09. 1031 records from ConDidact Citizen Science Surveys - Spiders 2011. 1 records from Madangella altirostris, a new genus and species of palaemonid shrimps (Crustacea: Decapoda: Palaemonidae) from Papua New Guinea. 268 records from Range table from benthic foraminifers in ODP Hole 159-959A. 72 records from Taxonomy and phylogeny of calcareous sponges (Porifera: Calcarea: Calcinea) from Brazilian mid-shelf and oceanic islands. 168 records from Roter Berg Werdau (Leubnitz). 2 records from Division of the genera Sparna Thomson, 1864 and Carterica Pascoe, 1858 (Coleoptera, Cerambycidae, Lamiinae, Colobotheini) with description of six new genera and eight new species. 7510 records from Données naturalistes de Charlotte PICARD. 2 records from A revision of the South American species of the ant genus Probolomyrmex (Hymenoptera: Formicidae).. 189 records from Total foraminifera counts of multinet M21/4_MSN706. 294 records from Plasm bearing foraminifera counts of multinet M21/1_MSN615. 4 records from The genus Sinodiaptera Dellacasa (Coleoptera: Scarabaeidae: Aphodiinae) in Taiwan. 346 records from FFH-Gebiet Klosterwasser/Burkau. 933 records from (Table S2) Relative abundance of coccolithophora in sapropel S1 of ODP Hole 160-964B, filtering preparation. 48 records from Abundance and carbon biomass of phytoplankton at station TT007_9-CTD113. 282 records from Biodiversity survey of Rugezi wetland, Year 2013. 63 records from Inventaire des espèces végétales de la vallée de Gounti Yéna (Niamey). 413 records from MLZ Bird Collection (Arctos). 449 records from Artsprosjekt Pyrenomycetes. 1577 records from (Table 2) Stratigraphic distribution of dinocyst taxa in ODP Hole 150-903A. 252 records from Naturschutzgebiet Müchelholz (Mücheln). 168 records from Assemblage of living benthic foraminifera in sediment core GeoB4916-4. 77 records from Microzooplankton abundance and biomass at station TT043_27-1. 332 records from Wiese am Waldrand (Gurtweil). 17 records from (Table 2.2.1.1) Abundance of sympagic meiofauna of sea-ice core IO-5. 2 records from Two new species of Nemouridae (Plecoptera) from Vietnam. 236 records from Birdrace-Birding_Bentheim-Grafschaft_Bentheim. 2168 records from Base de datos de las gramíneas (Poaceae) del noreste de México. 352 records from Renaturierung Werse (Innenbereich Beckum). 6 records from UWYMV Herpetology Collection (Arctos). 28 records from Meiofauna abundances at the Arctic Håkon Mosby Mud Volcano (HMMV) of sediment core PS64/390-1a. 41674 records from FUEL - Herbário da Universidade Estadual de Londrina. 8072 records from Inventario de larvas de peces en la región sur del Golfo de California (GAP 81, 85 y 86) y en el Pacífico Tropical Mexicano (GAP 88-91). 23746 records from Midden-Limburg Fish Ponds Survey. 17035 records from Dragonfly (Odonata) species records up to 1997 held by Leicestershire Environmental Resources Centre. 86 records from The cicada genus Procollina Metcalf, 1952 (Hemiptera: Cicadidae): redescription including fourteen new species, with a key to the species of the subtribe Dazina Kato, 1932 rev. stat., the description of the Aragualnini n. tribe, and one new combination. 54910 records from Herbarium Senckenbergianum (FR) - Fungi. 1808 records from Fish Collection of Coastal Branch of Natural History Museum and Institute, Chiba. 97 records from Assemblage of living benthic foraminifera in sediment core SO118_MC-02, 63-125 µm fraction. 40382 records from Seabirds in Norway - Estimated population sizes. 264 records from Range table from benthic foraminifers in ODP Hole 198-1207A. 190 records from Range table from benthic foraminifers in ODP Hole 189-1171C. 96 records from Range table from planktonic foraminifers in ODP Hole 139-855A. 7 records from Review of the Eulimnadia (Branchiopoda: Spinicaudata: Limnadiidae) from Argentina with the description of a new species. 247 records from Abundance of large foraminifera in cores from transect NOG-01B, IODP Expedition 325. 1316 records from Plant specimens of Bihoro Museum. 225 records from Plasm bearing foraminifera counts of multinet M21/5_MSN730. 24 records from Benthic macrofauna abundance of sediment core 12930-048. 2536 records from Mushroom Collection in BCRC. 294 records from Plasm bearing foraminifera counts of multinet POS247/2_MSN1381. 158 records from Planktic foraminifera counts at CTD station PS55/063. 227 records from Range table from benthic foraminifers in ODP Hole 174-1072A. 3449 records from Leicestershire and Rutland Aculeate Records. 2144 records from SPC CoFish Invertebrates Observations Marshall Islands 2007. 890 records from South Lanarkshire peatland records 2013. 12 records from A new genus and five new species of Anostostomatidae from the Lesser Antilles (Orthoptera: Ensifera). 30330 records from Suivi Temporel des Libellules (STELI). 8 records from Distribution of Quinqueloculina sp. in sediment core 13200-045. 1030 records from Étude entomologique des forêts publiques de Martinique, pour l'ONF. 138 records from Herpetological (amphibian & reptile) specimens of Ryukyu University Museum (Fujukan). 1243 records from Derbyshire Casual LEPIDOPTERA records - Casual records collated by Derby Museum.. 1644 records from Museo Nacional de Ciencias Naturales, Colección de Aves: MNCN-Ornit. 9011 records from Herbarium Specimens of Tokushima Prefectural Museum, Japan. 3841 records from Universidad Autónoma de Madrid, Madrid; Lepidópteros. 1141 records from RV Investigator Voyage IN2017_V02 Seabird Observations, Australia (2017). 1 records from Reptilia ZMK. 3772 records from University of Ghana - Ghana Herbarium. 4 records from Description of a new species of Eucynorta (Opiliones, Cosmetidae) from Cortés, Honduras. 3939 records from Census of plant species in Pahou forest reserve. 135 records from Computarización de la colección de myxomycetes y líquenes de Baja California. 5 records from Results of foraminifer and ostracode analyses of the Neogene of Hole 302-M0002A. 390 records from Truppenübungsplatz Panzerkaserne Böblingen. 651 records from Réseaux écologiques/Trame verte et bleue. 68 records from New data on brachypterous Paederus (Coleoptera, Staphylinidae) of mainland China. 8 records from Pseudoplesiops wassi, a new species of dottyback fish (Teleostei: Pseudochromidae: Pseudoplesiopinae) from the West Pacific.. 4 records from Notes on the Agrilus fauna of the Colombian Amazon (Coleoptera, Buprestidae). 16 records from Range table from dinoflagellates, acritarchs and prasinophytes in ODP Hole 191-1179C. 132328 records from Florida Keys Reef Visual Census 1996. 6 records from Zoology in the Middle East. 1988 records from Herbario virtual bosques secos de Colombia - Sección herbario ICESI. 7950 records from Segunda caracterización biológica de aves del proyecto "Incorporación de la Biodiversidad en el sector cafetero en Colombia". 95874 records from Données de l'Observatoire de la Faune de Bourgogne. 196 records from Revision of the genus Nephelomilta Hampson, 1900, with descriptions of twelve new species and two new subspecies (Lepidoptera, Erebidae, Arctiinae). 14 records from Review of the leafhopper genus Longicornus Li & Song (Hemiptera: Cicadellidae: Deltocephalinae) with description of two new species. 48774 records from Données de Luc BARBARO. 326 records from Host associations of Melanterius Erichson (Coleoptera: Curculionidae: Cleogonini), with a diagnosis and delimitation of the genus and description of five new species. 2097 records from Contribución al conocimiento taxonómico de los peces que habitan los sistemas acuáticos de la reserva de Calakmul, Campeche. 11 records from Range table from benthic foraminifers in ODP Hole 178-1096A. 2 records from A new species of Eigenmannia Jordan & Evermann (Teleostei: Gymnotiformes: Sternopygidae) from Río Ventuari, Venezuela. 1512 records from Mokihinui and Karamaea small tributaries and seeps. 8008 records from Museu de Ciències Naturals de Barcelona: MCNB-Tissue. 42 records from Sarcodine counts and carbon biomass at station TT012_5-PMOC5. 8674 records from Anillamiento de Aves Sierra Nevada de Santa Marta - Proyecto Cruzando el Caribe. 684 records from Relative abundances of late Quaternary benthic foraminifera in ODP Site 181-1119. 829 records from If_Ecologie_Conseil_2017_12_18. 2 records from Description of male Tylorida sataraensis Kulkarni, 2014 ( Araneae , Tetragnathidae ) with notes on habits and conservation status. 897 records from Range table from benthic foraminifers in ODP Hole 172-1063A. 420 records from Coleção Zoológica de Referência da Universidade Federal de Mato Grosso do Sul - Hemiptera (ZUFMS-HEM). 25 records from Colección de diatomeas del Herbario "Jaime Andrés Rodríguez". LEB-Diatomea. 915 records from Rescate de epífitas Oleoducto Bicentenario, Tramo Araguaney - Banadía (rescate). 38 records from Molecular and morphological identification of pistachio armored scale insects (Hemiptera: Diaspididae), with description of a new species. 85386 records from Allan Herbarium (CHR). 1104 records from Biological Recording in Scotland - Bumblebee Survey. 45311 records from Field Museum of Natural History (Zoology) Invertebrate Collection. 1392 records from Fortalecimiento de las colecciones de ECOSUR. Primera fase. 4 records from A new species of iguanid lizard, genus Stenocercus (Squamata, Iguania), from the Central Andes in Peru. 921 records from Royal British Columbia Museum Entomology Collection. 8174 records from Actualización de la base de datos de hongos macroscópicos de Jalisco. 19 records from Two new species of freshwater crayfish of the genus Faxonius (Decapoda: Cambaridae) from the Ozark Highlands of Arkansas and Missouri. 1 records from Lanlabeo duanensis, a new genus and species of labeonin fish (Teleostei: Cyprinidae) from southern China. 97 records from Monitoreo biológico en la cuenca La Paila, campaña ARA - RARE - CVC – Asociación Calidris. 2 records from The first elateroid beetles (Coleoptera: Polyphaga: Elateroidea) from the Upper Jurassic of Australia. 315 records from (Table 3) Meiofauna density in surface sediments of the Cretan Sea. 24 records from MVZ Herp Observations (Arctos). 496 records from Herrensee-Gebiet (Fischbachtal im Odenwald). 866 records from (Table 1) Distribution and numerical abundance of foraminifera of sediment core CRP-3. 4048 records from Mid-Pleistocene (800-400 ka) planktic foraminfer assemblages of IODP Site 306-U1314. 1029 records from Phytoplankton abundance in surface water in January 1996, Chimbote, Peru. 11880 records from Plan Aménagement et de Gestion Simplifié (PAGS) des forêts galeries des départements de l'Ouémé-Plateau. Data mobilized in the framework of a JRS Biodiversity Foundation project in Benin. 25 records from Inventario de Murciélagos Buenos Aires, Tauramena, Casanare. 8409 records from Aves Acuáticas de las sabanas inundables del Meta y Casanare. 3001 records from Colección Entomológica CDMB. 1 records from A new species of the subgenus Troginus Mulsant et Rey 1878 (Coleoptera: Staphylinidae: Oxytelinae: Carpelimus) from Borneo. 253 records from Données naturalistes d'Olivier LAURENT. 2 records from A new species of the Scinax catharinae group (Anura: Hylidae) from southeastern Brazil. 24260 records from Restauración y conservación de Isla Guadalupe. 6416 records from Lepidoptera (Specimens NRM). 1363 records from Mollusca specimens of Wakayama Prefectural Museum of Natural History. 500 records from Colección nacional de palmas de Colombia - JBQ. 1 records from First record of Myotis albescens (Chiroptera, Vespertilionidae) in French Guiana. 1986 records from ROC RSPB Farmland Species Survey Dataset. 196 records from Warnowtal (Rostock). 2854 records from (Table 2) Distribution of benthic foraminifera on sediment core PS2138-1. 404 records from Wild boar sightings held by Andy Riches. 2466 records from Las comunidades de myxomicetes de selva baja caducifolia. 6 records from Wuhle - Brücke / B1. 364098 records from Florida Keys Reef Visual Census 1999. 32 records from New enigmatic species of the genus Pediobius (Hymenoptera, Eulophidae) from Afrotropics, with notes on related genera. 9077 records from Marie-Victorin Herbarium (MT) - Bryophytes. 218 records from (Fig. 5a) Limacina dissolution index of sediment core GeoB2205-4. 310 records from Código de barras de ejemplares de la Colección Nacional de Mamíferos del Instituto de Biología, UNAM. 1 records from Three Echiniscidae species (Tardigrada: Heterotardigrada) new to the Polish fauna, with the description of a new gonochoristic Bryodelphax Thulin, 1928. 12646 records from Collection of saproxylic and xylobiont Beetles. 1562 records from Composición florística y estructura de tres parcelas permanentes en diferentes estados sucesionales en transición de bosques húmedos tropicales con bosques secos tropicales del municipio de Lebrija, Santander (Primer censo). 110 records from Range table from planktonic foraminifers in ODP Hole 144-875C. 415 records from Caracterización de vegetación para el establecimiento de límites funcionales de humedales: Ciénaga de la Virgen, Ciénaga Zapatosa y Complejo Hato Corozal - Paz de Ariporo. 222 records from BIRDRACE Die Wendehälse. 58623 records from Tachinid Recording Scheme - GB and Ireland records. 429 records from Abundance and biomass of phytoplankton in Butakova Bay, Aral Sea, in september 1990. 32 records from Review of genus Hydropsyche Pictet 1834 (Insecta: Trichoptera: Hydropsychidae) from India. 300 records from Phytoplankton abundance and species composition in the Gulf of Naples in June 1999 at station MCSSII-phyto120-128. 4617 records from Données de type contact de Guadeloupe. 39 records from Range table from benthic foraminifers in ODP Hole 178-1103A. 186 records from Range table from planktonic foraminifers in ODP Hole 170-1041A. 3 records from Naturalis Biodiversity Center (NL) - Pisces. 244406 records from Carnet B Lorraine. 1037 records from Evaluación del estado actual de las poblaciones silvestres de chigüiros (Hydrochoerus hydrochaeris) en los municipios de Paz de Ariporo y Hato Corozal, Casanare. 18 records from Halaelurus maculosus n. sp. and H. sellus n. sp., two new species of catshark (Carcharhiniformes: Scyliorhinidae) from the Indo-West Pacific.. 1353 records from Counting of benthic foraminifera of ODP Hole 182-1132B. 705 records from (Table 1) Pleistocene planktonic foraminiferal assemblages at ODP Site 128-798. 1117 records from Radiolaria assemblage in sediment core GIK23414-6. 31788 records from Observatoire de la Biodiversité des Jardins (OBJ). 282 records from Myxomycetes collection of the University of Eastern Finland. 28 records from Black fungus gnats (Diptera: Sciaridae) found in association with cultivated plants and mushrooms in Australia, with notes on cosmopolitan pest species and biosecurity interceptions. 548656 records from Seasearch Marine Surveys in England. 387 records from Plasm bearing foraminifera counts of multinet M21/2_MSN657. 108 records from Données de Mammifères marins dans les TAAF et autres territoires issues de la bibliographies. Compte cardobs 1007 (Trudelle). 182 records from Late Albian Col de Palluel (SE France, Niveau Breistroffer): results from planktic foraminifera. 308 records from Tejidos de la expedición en el páramo de Rabanal, Boyacá - Proyecto Boyacá BIO. 12 records from Revising the generic characters of Lobogonodes Bastelberger, 1909, with description of a new species from Taiwan (Lepidoptera: Geometridae: Larentiinae). 1320 records from Collection Trichoptera - SMF. 1 records from Macrochelid mites (Mesostigmata: Macrochelidae) from São Paulo state, Brazil, with description of a new species of Macrocheles. 324 records from Integrierte Gesamtschule Flensburg Wiemoosgraben. 12 records from Seven new species of the Stenus cirrus group (Coleoptera, Staphylinidae) from Guangxi, South China. 6263 records from Range table from nannofossils in ODP Hole 164-994C. 79 records from The genus Leucophenga (Diptera, Drosophilidae), part VII: the subpollinosa species group from China, with morphological and molecular evidence. 130 records from Abundances of dinoflagellate cysts in sediment trap MST-9 (Appendix 1). 754 records from Range table from planktonic foraminifers in ODP Hole 182-1127B. 23 records from Range table from dinoflagellates, acritarchs and prasinophytes in ODP Hole 159-962D. 554 records from Pollen analysis of sediment core GeoB6518-1. 10 records from Three new taxa of Noctuidae from China (Lepidoptera: Noctuidae). 18468 records from Arizona State University Hasbrouck Insect Collection. 11 records from Description of lithologic section units of IODP Hole 325-M0055A. 25590 records from CCAMLR historic KRILL. 99 records from (Table 2) Abundance of benthic foraminifers of sediment core PS2139-1. 490 records from Quarrendorfer Landschaftsschutzgebiet. 324 records from Registros de quirópteros de tres localidades del caribe colombiano. 3755 records from Fortalecimiento de las colecciones de ECOSUR. Primera fase. 1015 records from Inventario ictiofaunístico de los humedales de Puerto Morelos, Quintana Roo. 248 records from Birdrace-Die_Ackermännchen-Schalm-Eder-Kreis. 60 records from New record of the pentatomine stink bug species Caystrus orientalis Zhang and Lin (Hemiptera: Pentatomidae) from Japan. 44 records from Kuhwiese Beerentaltrift (Hamburg/ Harburg). 2 records from Lizards in pinstripes: morphological and genomic evidence for two new species of scincid lizards within Ctenotus piankai Storr and C. duricola Storr (Reptilia: Scincidae) in the Australian arid zone. 6186 records from Establecimiento de un área protegida en el Alto y Bajo Calima, área clave de biodiversidad en el Valle del Cauca, Colombia. 13893 records from Enquête Lucane. 115 records from Phytoplankton abundance at station Casma_2003-04-28_2, Casma, Peru. 2618 records from CSIC-Real Jardín Botánico-Colección de Algas (MA-Algae). 1922 records from Erlengraben/Lipp-Tal (Östringen). 95 records from ZUEC-ECH - Coleção de Echinoidea do Museu de Zoologia da UNICAMP. 2006 records from Relative abundance of Neogene nannofossils at ODP Site 165-998 from the Caribbean. 6574 records from Birds of Rottnest Island, Western Australia, 1981 - 2007. 1922 records from Données Cetonidae -1981-2014-LACOSTE Frédéric. 28 records from Different continents, same species? Resolving the taxonomy of some Holarctic Ancylis Hübner (Lepidoptera: Tortricidae). 1832 records from Herbier National de Guinée (HNG). 441 records from Plasm bearing foraminifera counts of multinet M21/2_MSN656. 4 records from A new species of the genus Diogenes Dana, 1851 (Crustacea: Decapoda: Anomura: Diogenidae) from Gujarat, northwestern India. 392 records from Expédition Karubenthos 2012 : inventaire des Echinodermes de la Guadeloupe. 11943 records from EDIT - ATBI in Gemer area (Slovakia). 8 records from Revision of Afrotropical Silky Lacewings (Neuroptera: Psychopsidae). 32 records from New species of Neohybos Ale-Rocha & Carvalho (Diptera, Hybotidae, Hybotinae) from South America. 42762 records from Global compendium of Aedes albopictus occurrence. 596 records from Colección de Herpetología de la Universidad del Quindío (HERPETOS-UQ). 304 records from BioGIS - Reptiles - HUJ collections. 176 records from Teich Berlin Wuhlheide. 19 records from Microplankton data off Mejillones, 2006, Chile. 4523 records from UTEP Vertebrates. 112 records from Creag Riabhach Wind Farm: 2012-13 Ornithology and Protected Mammal Surveys. 300 records from AKG-Gelände (Bensheim). 940364 records from Flora Atlas N.T.. 28 records from Sarcodine counts and carbon biomass at station TT012_5-TM9. 1 records from Klosterlandschaft Maulbronn 19. und 20. Juni 2010. 14 records from Redescription of Cletocamptus albuquerquensis and C. dominicanus (Harpacticoida: Canthocamptidae incertae sedis), and description of two new species from the US Virgin Islands and Bonaire. 4 records from Paracercion ambiguum sp. nov. from Lang Son, Vietnam (Zygoptera: Coenagrionidae). 3 records from A new species of velvet skate, Notoraja sereti n. sp. (Rajiformes: Arhynchobatidae) from Papua New Guinea. 9820 records from Respaldo de las colecciones de tejidos del Museo de Zoología, Departamento de Biología Evolutiva, Facultad de Ciencias, UNAM. 42 records from Nano and microzooplankton abundance and biomass at station NBP96-04A-13-4. 708 records from Naturschutzgebiet Heiliger Hain (Wahrenholz). 3 records from A new species of Dohrnemesa from Brazil, with notes on the male of D. carvalhoi and on D. albuquerquei (Hemiptera: Heteroptera: Reduviidae: Emesinae). 24 records from Revision of the genus Amytta (Orthoptera: Tettigoniidae, Meconematinae) and new species from East Africa. 76 records from Atomariine Beetle (Coleoptera) records for Britain and Ireland to 1992. 15586 records from Colección Ictiológica del Instituto Alexander von Humboldt. 845 records from Alterra (NL) - Entomofauna inventory in arable fields Hoeksche Waard. 139 records from Occurrence of zoobenthos organisms in the sampled Central-Yakutian Lakes, Appendix 2-4. 899 records from Stable isotopes and content of foraminifera at Hole 130-805C. 93 records from Caddisflies (Insecta: Trichoptera) from Maranhão State, Northeast Region, Brazil: A new species, checklist, and new geographical records. 529 records from Colección de Referencia de Macroinvertebrados Bentónicos del Museo de Ciencias de la Universidad El Bosque. 50 records from Microzooplankton abundance and biomass at station NBP97-08-05-1. 1169 records from Colección base (BGVPA) del Banco de germoplasma del Jardín Botánico Atlántico de Gijón. 4 records from Revision of the Genus Leptogomphus Selys in Borneo, including gene trees and a two marker molecular phylogeny (Odonata: Anisoptera: Gomphidae). 2 records from Towards a robust systematic baseline of Neotropical fish tapeworms (Cestoda: Proteocephalidae): amended diagnoses of two genera from the redtail catfish, Phractocephalus hemioliopterus. 420 records from Lebensraum Gesamtschule (Langerwehe). 13 records from Proyecto interno ejecutado por la CONABIO: Sistema de información sobre Bosque Mesófilo de Montaña de México para apoyo en programas de restauración (Fase 1). 63967 records from Butterflies of Ireland. 706 records from Rare plants database extract from Scottish Natural Heritage. 879 records from (Table 3) Distribution of benthic foraminifera in ODP Hole 183-1138A. 17 records from Range table from planktonic foraminifers in ODP Hole 139-856C. 2905 records from (Table A.01) Planktic foraminiferal census data of sediment core GIK23414-9. 798 records from Coléoptères Silphidés du département du Loiret. 8789 records from SP-Algae - Herbário do Estado "Maria Eneyda P. Kaufmann Fidalgo - Coleção de Algas. 355 records from Total foraminifera counts of multinet M21/2_MSN648. 136792 records from CSIRO, Cruises, Vertebrate and Invertebrate Fishery Bycatch, North Australia, 1997. 23011 records from Formidabel; Belgian Ants Database. 3272 records from Mammifères marins Guadeloupe Antilles françaises (AET). Suppléments. 118 records from Observation des insectes sur le territoire de la Métropole Rouen Normandie. 192 records from Alterra (NL) - Microarthropods inventory in Cranendonck area. 479 records from Anfibios y reptiles de la Sierra Montenegro-Las Trincheras y el cerro el Chumil, Morelos. 190 records from A checklist of the Cleridae of Iran with new data (Coleoptera: Cleroidea). 354 records from Tejidos colectados en la caracterización biótica para la conservación de especies amenazadas en el área de influencia del Oleoducto Bicentenario, departamentos de Arauca y Casanare, Colombia. 16 records from Hazel Dormouse in Ireland. 164 records from Range table from planktonic foraminifers in ODP Hole 167-1021B. 2 records from A new species of Pseudocrenilabrus (Perciformes: Cichlidae) from Lake Mweru in the Upper Congo River System. 108927 records from CAS Invertebrate Zoology (IZ). 341 records from Range table from planktonic foraminifers in ODP Hole 171-1053A. 20 records from A checklist of the Ukrainian Xoridinae (Hymenoptera, Ichneumonidae). 123 records from Total foraminifera counts of multinet M21/4_MSN694. 4 records from Rivulus uatuman sp. n. (Teleostei: Cyprinodontiformes: Rivulidae): a new miniature killifish from the central Brazilian Amazon.. 8 records from Distribution of Quinqueloculina sp. in sediment core 12930-014. 78414 records from Insects, Outer Hebrides. 334 records from Taxonomía y distribución de los filópodos (Crustacea: Branchiopoda, Anostraca, Notostraca, Spinicaudata y Laevicaudata) de México. 204 records from Annotated catalog of the type specimens deposited at the fish collection of the “ Universidade Estadual Paulista, Câmpus de São José do Rio Preto ”, São Paulo, Brazil (DZSJRP). 92 records from An der Ohm, (Wettsaasen). 99 records from Phytoplankton abundance at station Rigel_4_2005-08 in August 2005, Chipana, Chile. 336 records from Restauración de flora y repoblamiento de fauna nativa en 1,000 hectáreas para el restablecimiento del corredor biológico costero en la Laguna Madre, Tamaulipas. 7445 records from BioGIS - Vascular plants - Israeli Gene Bank. 5 records from Range table from planktonic foraminifers in ODP Hole 169-1038E. 10 records from Taxonomic revision of Intybia Pascoe, 1886 species (Coleoptera, Malachiidae) of Thailand and Philippines. 7958 records from NSW South Coast & ACT plants. 184 records from Radiolaria assemblage in sediment core GIK23400-3. 1 records from A New Species of Deep-channel Electric Knifefish Compsaraia (Apteronotidae, Gymnotiformes) from the Amazon River. 701 records from Range table from benthic foraminifers in ODP Hole 151-913B. 412 records from Phytoplankton abundance at stations off Punta Falsa in August 1995, Piura, Peru. 148 records from Abundance of birds in the Lena Delta Region. 73 records from Rhopalocères du PNR Périgord Limousin au 15/10/2015. 99 records from Range table from planktonic foraminifers in ODP Hole 139-855C. 59 records from Succession of benthic hard-bottom communities abundance at station Errina2012_CS. 3604 records from Phytoplankton abundance during Arnold Veimer cruise AV90/2. 2297 records from (Table 16) Distribution of planktonic foraminifera in the late Paleocene to earliest Oligocene section of ODP Hole 149-900A. 248 records from Kirkliston Range stream monitoring. 5 records from A new species of cave dwelling Neocarus (Acari: Opilioacaridae) from Bahia state, Brazil, with remarks on taxonomic characters. 66 records from Museo Provincial de Ciencias Naturales “Florentino Ameghino”, Santa Fe, Argentina - Colección Squamata (no Serpentes) (MFA-ZV-Sq). 42 records from An der Weida zwischen Talsperre Zeulenroda und Vorsperre Weida. 35 records from Ortsrand Zandershagen. 141 records from Plasm bearing foraminifera counts of multinet POS247/2_MSN1384. 7 records from A new genus and species of owlfly from eastern and southern Africa (Neuroptera: Ascalaphidae). 16370 records from Akita Prefectural Museum, Observation Records of Birds in Akita Prefecture. 1010 records from National Frog Survey of Ireland 2010/2011. 228 records from Chironomid remains in the sediment sequence of Site PG1212. 3290 records from MGC Herbarium of University of Malaga (Spain): MGC-Algae dataset. 11 records from Range table from benthic foraminifers in ODP Hole 139-856C. 395 records from Range table from planktonic foraminifers in ODP Hole 170-1039B. 5 records from Dryinidae and Embolemidae (Hymenoptera, Chrysidoidea) from Anijima, Ogasawara Islands, Japan. 29 records from Descriptions of four new species of Semia Matsumura (Hemiptera: Cicadidae: Psithyristriini) from Vietnam, with a key to the species of Semia. 1721 records from Lista florística de la Costa Grande del estado de Guerrero. 47 records from Range table from planktonic foraminifers in ODP Hole 169-1036B. 30 records from Espèces envahissantes de la Guinée forestière extraites dans la base de données de CRRA Sérédou Macenta, IRAG.. 6549 records from Abundance of organic-walled dinoflagellate cysts of sediment core GeoB3603-2. 2023 records from (Appendix 6) Benthic foraminifera at termination I in sediment core PS1906-2 in the Greenland Sea. 457 records from Helmintos parásitos de peces dulceacuícolas de cuencas hidrológicas del Centro-Norte de México (Durango). 124056 records from MDFRC macroinvertebrate survey. 239 records from Données naturalistes de Pauline BALDUCCI. 124 records from Amtsrain Apolda-Zottelstedt. 142 records from Phytoplankton abundance measured on water bottle samples during Jan Mayen cruise JM1. 4761 records from USGS ASC - Yukon Kuskokwim River Delta - Birds - 1992-2002. 47376 records from Diversidad y dinámica del fitoplancton marino en la bahía de Acapulco, Guerrero. 16 records from A revision of the genus Medmassa Simon, 1887 (Araneae: Corinnidae) in the Afrotropical Region. 49 records from Calcareous sponges of the Western Indian Ocean and Red Sea. 2 records from A new species of Polietina (Diptera: Muscidae) from South America, with an updated phylogeny of the genus and a review of species’ identity in GenBank. 88 records from Microplankton abundance at Station MARCH-1998-GN36199804611MNB03 in the euphotic zone of the Aegean Sea in March 1998. Part 2 - dinoflagellates. 13017 records from Muséum_de_Toulon_et_du_Var_2017_12_18. 17 records from Description of lithologic section units of IODP Hole 325-M0043A. 14 records from Grundwasserlebensraum im Englischen Garten (München). 1993 records from Inventario de macroalgas de Isla Guadalupe, México. 8 records from The socially parasitic ant genus Strongylognathus Mayr in North Africa (Insecta: Hymenoptera: Formicidae).. 213 records from Crustacea in surface sediments off Sylt collected during HEINCKE cruise HE218. 70 records from Range table from planktonic foraminifers in ODP Hole 167-1010E. 4 records from A new species of the swimming crab genus, Laleonectes Manning & Chace, 1990 (Crustacea: Brachyura: Portunidae), from the western Indian Ocean. 20 records from Review of East Palaearctic species of Sympycnus Loew, 1857, with a key to species. 2893 records from The Collection of Lichenicolous Fungi at the Botanische Staatssammlung München. 19364 records from (Table 1) Stratigraphic ranges of planktonic foraminifers in ODP Hole 144-871A. 436 records from Colección Thomas G. Zoebisch asociada a la Colección Entomológica del Centro de Estudios en Zoología. 31550 records from MCP - Coleção de Abelhas. 123 records from Microplankton abundance at Station MARCH-1997-GN36199704603MNB03 in the euphotic zone of the Aegean Sea in spring 1997. Part 2 - dinoflagellates. 52 records from Erhard Sopp. 478 records from Echinoderms in surface sediments off Sylt collected during HEINCKE cruise HE293. 26 records from Die Oribatiden-Arten (Acari) eines suedwestdeutschen Buchenwaldes I.. 70 records from Taxonomic studies on potter wasps (Hymenoptera: Vespidae: Eumeninae) of south India. 415 records from Macrobenthos in surface sediments off Sylt collected during HEINCKE cruise HE206. 1966 records from DNA barcoding the fishes of Lizard Island (Great Barrier Reef). 197 records from Dorfrand Mauderode. 134 records from Abundance of planktic foraminifera at CTD station PS55/082-1. 1 records from Eucharitidae new to the fauna of Saudi Arabia (Hymenoptera: Chalcidoidea), with the description of a new species and the previously unknown male of Eucharis (Psilogastrellus) albipennis Bouček. 122 records from Shrews of Poland. 41 records from Abundance of living benthic foraminifera in sediment core CD86_07_BC4. 180 records from Données naturalistes de Pascal Dupont. 5725 records from Pautas para el manejo y ordenamiento de una pesquería multiespecífica de crustáceos en un área natural protegida: El caso de la Ría Celestún, Yucatán. 10 records from New distributional records and life stage description of Caenis species (Ephemeroptera: Caenidae) from Brazil. 348 records from Microzooplankton abundance measured on water bottle samples at station PS58/061-1. 23233 records from TPWD HARC Texas Coastal Fisheries Corpus Christi Bay Bag Seine. 224 records from Bird specimens of Bihoro Museum. 1 records from Discovery of a new species of Dryocosmus Giraud, 1859 (Hymenoptera: Cynipidae: Cynipini) on Castanopsis tibetana from China. 243 records from (Table 2.2.2.1) Integrated abundance of sympagic meiofauna in sea-ice cores of Aurora Australis cruise SIPEX. 1308 records from Phytoplankton abundance in surface water in May 1996, Ilo, Peru. 2 records from Wie viel Natur gibt es im Park?. 3061 records from Nematode abundance in sediments obtained during the Belgica cruise BG06/13, Gollum Channels and Whittard Canyon. 79 records from UNIVATES - Coleção de Ornitologia do Museu de Ciências Naturais da Universidade do Vale do Taquari - Univates (ZOUMCN-UNIVATES). 81968 records from Marine benthic dataset (version 1) commissioned by UKOOA. 592 records from Occurence of marine palynomorphs of sediment core CRP-1 (Table 1). 1970 records from Freshwater Fishes of Bulgaria. 59752 records from European Moth Nights. 8 records from Abundance of microplankton from bottle APRIL-2000-K3. 103 records from Range table from planktonic foraminifers in ODP Hole 177-1089D. 480 records from Inventaire des Crustacés Décapodes de France métropolitaine. Données du compte CardObs 1113. 7420 records from NBMB Herps. 1390 records from Database on reference specimens for medicinal plants of the Fabaceae family, conserved at the CNARP herbarium. 1 records from Description of the imago of Neocapritermes utiariti (Isoptera: Termitidae: Termitinae). 931 records from Données naturalistes de Mathilde DUSACQ. 2068 records from Colecta botánica: área maya región de la Reserva Calakmul, Campeche. 49164 records from USU-UTC Specimen Database. 3018 records from SPC PROCFish/C Invertebrates Observations Wallis and Futuna 2005. 5979 records from Efectos del Cambio Ambiental en las comunidades de organismos de los ríos mediterráneos. 1577 records from Registro de vertebrados durante el fototrampeo del convenio 027 - 2014 CVC - Panthera. 620 records from Umgebung der Gesamtschule Hamburg-Winterhude. 8 records from Description And Phylogeny Of Staminodeus, A New Genus Of Derelomini (Coleoptera: Curculionidae) Associated With Cyclanthaceae. 2072 records from BUND - Dassower See (Lübeck/Dassow). 6072 records from (Table AT1) Planktonic foraminiferal stratigraphy of ODP Hole 182-1126B. 1056 records from Birds and plant species near Petushki town (Vladimir region). 597 records from Revues diverses et littérature grise.. 7 records from Description of lithologic section units of IODP Hole 325-M0050A. 1 records from Chaetanaphothrips kiyosumianus (Thysanoptera, Thripidae) new to India with first record of the male. 616 records from Surface seawater carbonate chemistry, nutrients and phytoplankton community composition on a transect between North Sea and Arctic Ocean, 2008. 100 records from Lindesnes. 6067 records from Arthur Chapman Observations. 1128 records from Cuxhavener Küstenheiden. 10 records from Two new species of genus Lasiosina Becker from China (Diptera, Chloropidae). 21908 records from UMMZ Birds Collection. 1 records from Meatopida gen. nov., a new genus to accommodate two species originally described in Atopida White, 1846 (Coleoptera: Scirtoidea: Scirtidae). 238 records from UWYMV Bird Collection (Arctos). 1506783 records from Hatikka Observation Database. 86 records from Range table from planktonic foraminifers in ODP Hole 183-1139A. 649 records from Distribution of benthic foraminifera on sediment core sediment core PS2458-4. 131784 records from inatura - Erlebnis Naturschau Dornbirn. 5 records from Systematics of the Mesalina guttulata species complex (Squamata: Lacertidae) from Arabia with the description of two new species. 441 records from Range table from dinoflagellates, acritarchs and prasinophytes in ODP Hole 159-959D. 16 records from On the genus Tylorida Simon, 1894 with the first record of the genus Atelidea Simon, 1895 from India (Araneae: Tetragnathidae, Leucauginae). 76 records from (Table 1) Counts and concentrations of pollen, spores and dinoflagellate cysts in sediment core MD01-2378. 2 records from A new species of Masteria L. Koch, 1873 (Dipluridae: Masteriinae) from Guyana. 25 records from Collection Graptolithina fossil SMF. 771 records from Colección de reptiles del Museo de Historia Natural de la Pontificia Universidad Javeriana. 2 records from Chinja, a new genus of spider from the Eastern Arc Mountains of Tanzania (Araneae, Zoropsidae). 47292 records from Specimen Database of Colorado Vascular Plants. 1924943 records from PlutoF platform observations. 25953 records from Diatomeas (Bacillariophyceae) y dinoflageladas (Dinophyceae) frecuentes en el Pacífico mexicano (costa oeste de Baja California, Pacífico centro y sur). 6 records from Two new species of Corumbataia (Hypoptopomatinae: Loricariidae) from Rio Corrente, upper Rio Paraná basin, Brazil. 654 records from Occurrence data of Swallowtail butterflies (Lepidoptera: Papilionidae) in the Zoology Museum of Makerere University. 6 records from Four species of Tubifex Lamarck (Annelida: Oligochaeta: Naididae) from Tibet, China. 124 records from Taxonomic and nomenclatorial revision within the Neotropical genera of the subtribe Odontocheilina W. Horn in a new sense— 18. Six Mexican and Central American species related to Odontocheila mexicana Laporte de Castelnau and O. ignita Chaudoir, with a description of O. potosiana sp. nov.. 392 records from Total foraminifera counts of multinet M21/6_MSN784. 31 records from Range table from planktonic foraminifers in ODP Hole 181-1119C. 21 records from Benthic macrofauna abundance of sediment core 13078-015. 8 records from The genus Spirontocaris Spence Bate, 1888 (Caridea, Decapoda, Thoridae) in western Mexico. 103 records from Megafauna of the UKSRL exploration contract area and eastern Clarion-Clipperton Zone in the Pacific Ocean: Annelida, Arthropoda, Bryozoa, Chordata, Ctenophora, Mollusca. 124 records from Zoo Frankfurt. 440 records from Propuesta para rescatar y conservar la paleobiota de la Cantera Tlayúa, en Tepexí de Rodríguez, Puebla: Fase II. 258 records from BIRDRACE Oostfreesland Bird-Lopers. 238 records from Données Mammifères marins Aquasearch - Dauphin Passion. 354 records from Canada_BasinMegabenthos2002. 363 records from Total foraminifera counts of multinet M10/2_MSN262. 164 records from (Table 7) Percent distribution of calcareous nannofossils at ODP Hole 125-786A. 20 records from Description of lithologic section units of IODP Hole 325-M0033A. 218 records from Birdrace-Di_Bi_Di_Birder-Wesel. 453 records from Range table from planktonic foraminifers in ODP Hole 182-1129C. 4348 records from ConDidact Citizen Science Surveys - Snails 2006. 46 records from New species and records of Leuctridae (Plecoptera) from Guangxi, China, on the basis of morphological and molecular data, with emphasis on Rhopalopsole. 16 records from Caddisflies (Insecta: Trichoptera) from Santa Catarina Lachatao, Oaxaca, México: New species, new geographical records, and checklist. 25 records from Base de données en ligne d'observations naturalistes de mammifères marins. www.faune-guyane.fr. GEPOG & LPO. 47 records from (Table 1.2.1.1) Abundance of sympagic meiofauna of sea-ice core PS69/549-2. 152 records from Total foraminifera counts of multinet M21/5_MSN742. 198 records from Schwanner Warte / Kinderhaus St. Elisabeth Waldplatz. 4944 records from Base de datos de la flora de la Reserva de la Biosfera Chamela-Cuixmala, Jalisco, México. 702 records from Orchideenstandort Nostengraben - Kretzberg (Oßmaritz). 564 records from Deponie Klausdorf. 94 records from Schulgelände (Wetter). 75 records from Myrmeleon almohadarum sp. nov., from Spain and North Africa, with description of the larva (Neuroptera Myrmeleontidae). 2 records from First records of the jewel beetles Chrysobothris desmaresti (Laporte & Gory, 1836) and Hiperantha stempelmanni Berg, 1889 (Coleoptera: Buprestidae) in Bolivia. 47 records from Canadian Museum of Nature Palynology Collection. 122 records from Macrofauna biomass in surface sediment sampled during cruise DI231. 168 records from Microzooplankton abundance measured on water bottle samples at station PS65/570-4. 748 records from Herpetofauna de la región del Mar Muerto, Oaxaca-Chiapas. 1284 records from Données naturalistes de Thomas LORICH. 84 records from "Natur macht Schule 2" Natur im Wohngebiet Gorndorf. 30 records from Abundance, biovolume and biomass of heterotrophic dinoflagellates at station TT011_5-CTD58. 262 records from Microplankton abundance at Station MARCH-1997-GN36199704601MSB07 in the euphotic zone of the Aegean Sea in spring 1997. Part 1 - diatoms. 2 records from New records of Solenocera barunajaya Crosnier, 1994 and Solenocera rathbuni Ramadan, 1938 (Crustacea: Decapoda: Penaeoidea) from the southwest coast of India. 120 records from Range table from benthic foraminifers in ODP Hole 172-1060B. 15 records from Three new species of Holoscolex (Clitellata, Glossoscolecidae) from the Gurupi Biological Reserve, last forest remnant of the Belém Endemism Area, Eastern Amazon. 2039 records from Atlas des Poissons et Crustacés d'eau douce de Guadeloupe. 29578 records from CAS Entomology (ENT). 2 records from A new blind snake of the genus Letheobia (Serpentes: Typhlopidae) from Rwanda with redescriptions of L. gracilis (Sternfeld, 1910) and L. graueri (Sternfeld, 1912) and the introduction of a non-invasive preparation procedure for scanning electron microscopy in zoology. 1275 records from Biodiversidad de productores primarios de las lagunas costeras del norte de Yucatán. 1203317 records from Fungal Records Database of Britain and Ireland. 1249 records from (Table 2) Biostratigraphy of marine benthic and planktonic taxa in sediment core GIK14350 near Dagebüll, northern Germany. 1 records from Redescription and biology of Gonatopus amazonicus Olmi (Hymenoptera, Dryinidae) from Southern Brazil. 26915 records from Insect specimen database of Atsugi City Museum. 20150 records from Nematoda of Costa Rica (INBio). 5 records from A checklist of seed-beetles (Coleoptera: Chrysomelidae: Bruchinae) from Iran. 213 records from Tejidos de especimenes colectados en la ventana de biodiversidad Río Guamués, corregimiento El Encano, Municipio de Pasto, Nariño, Colombia. 451 records from Total foraminifera counts of multinet M21/2_MSN643. 32 records from A review of the genus Orionis Shaw (Hymenoptera: Braconidae: Euphorinae) and first records of the genus from South America and the Oriental Region. 160 records from Occurrence Data of Small Carnivores (Mammalia, Carnivora) in the National Museums of Kenya Zoology Collection. 472 records from Capercaillie national surveys. 16043 records from La familia Asteraceae en México. Fase VI. 712 records from Morphologische Daten von Puffinus creatopus. 725 records from (Table 3) Protist occurrence in bottom sea ice and surface water samples obtained during a CCGS Amundsen cruise in 2007/2008. 24414 records from WTSWW Data: All Taxa (West Wales). 40 records from Fichas diagnósticas para 10 especies de anfibios y reptiles mexicanos. 825 records from (Appendix A5) Relative abundances of planktonic foraminifera of sediment core GeoB1711-4. 822914 records from Cartografía de vegetación a escala de detalle 1:10.000 de la masa forestal de Andalucía. 1 records from Two new species of Tenuipalpus Donnadieu, 1875 (Acari: Trombidiformes: Tenuipalpidae) from Iran. 258 records from Mycological collection of the National Museum. 126 records from Marine gastropod distribution from patagonian shallow waters. 384 records from "Ahrschleife bei Altenahr". 18 records from A new species of Leuctra from Turkey, and notes on Anatolian Rhabdiopteryx (Plecoptera: Leuctridae & Taeniopterygidae). 216 records from Range table from benthic foraminifers in ODP Hole 174-1073A. 268391 records from South Australian Museum Australia provider for OZCAM. 4 records from Two new Thiratoscirtus species from Gabon (Araneae, Salticidae, Thiratoscirtinae). 18 records from Documenting diversity in the Amazonian butterfly genus Bia (Lepidoptera, Nymphalidae). 133 records from Plasm bearing foraminifera counts from multinet M32/3_MSN957. 95 records from Phytoplankton abundance at station Rigel_4_2005-05 in May 2005, Chipana, Chile. 23 records from Coccolith counts of multinet M32/5_MSN981. 40 records from Herbarium BSG Hepaticopsida. 2 records from Brock University Herbarium (BU). 240 records from (Table 1) Distribution of planktonic foraminifers in ODP Hole 126-787B. 21 records from Sarcodine counts and carbon biomass at station TT008_6-PMOC7. 4009 records from DASSH Data Archive Centre volunteer survey data. 821946 records from Ministerio de Medio Ambiente, y Medio Rural y Marino. Dirección General de Medio Natural y Política Forestal. Inventario Nacional de Biodiversidad 2007, Aves Reproductoras. 1732 records from Biodiversidad vegetal de la parte alta oeste de la cuenca del Chuviscar, Chihuahua. 138 records from Unter hellen Zinnen und finsteren Grotten. 48 records from Biopearl expedition: SeaStars (Echinodermata, Asteroidea). 149 records from Range table from planktonic foraminifers in ODP Hole 177-1088C. 254 records from BIRDRACE Immerwiederhopf. 17 records from An annotated taxonomic checklist of the Neotropical Gracillariidae (Lepidoptera) with links to the information on host plants and parasitoids. 27 records from Plasm bearing foraminifera counts from multinet M31/2_MSN890. 7 records from Description Of Six New Species Of Spiders Of The Genera Lathys (Family: Dictynidae), Marpissa (Family: Salticidae), Misumenoides (Family: Thomisidae), Agroeca (Family: Clubionidae), Gnaphosa (Family: Gnaphosidae) And Flanona (Family: Lycosidae) - From India. 12346 records from SPC PROCFish/C Fish Observations New Caledonia 2004. 170 records from Range table from planktonic foraminifers in ODP Hole 177-1089B. 5 records from A description of three new species of the genus Alienia Fibiger, 2011 from Southeast Asia (Lepidoptera, Erebidae, Hypenodinae: Micronoctuini). 19338 records from Modernisation des ZNIEFF du PnrL. 2 records from A review of Garra (Teleostei: Cypriniformes) from two rivers in West Yunnan, China with description of a new species. 48 records from Dinoflagellate cysts of surface sediments. 1 records from Collection Malakologie - SMNG. 601 records from Muestreos y recolectas de flora endémica y casi-endémica de matorral costero y chaparral de la zona mediterránea Baja California, México. 47 records from Données d'observation de phanérogames marines en Martinique. 42 records from UWIZM Cnidarians. 42 records from A review of the Tillicera genus group with a revision of Plathanocera Schenkling (Coleoptera, Cleridae, Clerinae). 2118 records from irregularia_mexico. 354 records from Antarctic and Subantarctic Asteroid zoogeography. 3 records from New species and records of Omaliini from East Asia (Coleoptera: Staphylinidae: Omaliinae). 5 records from Microzooplankton abundance and biomass at station TT050_25-4. 374 records from Coastal and Marine Species Database. 133850 records from Tasmanian Museum and Art Gallery provider for OZCAM. 200 records from Data from vegetation plots at Atiquipa, Southern Peru. 3 records from TTRS Mammals. 108 records from Weidegebiete in der Selzrenaturierung. 35 records from Revision of the genus Dinotoperla Tillyard, 1921 (Plecoptera: Gripopterygidae) using morphological characters and molecular data: Establishes two new genera, three new species and updates the larval taxonomy. 744 records from Ostracoda in sediment core PS51/159-10. 2 records from A global revision of the Seahorses Hippocampus Rafinesque 1810 (Actinopterygii: Syngnathiformes): Taxonomy and biogeography with recommendations for further research. 4 records from Lampetra soljani, a new brook lamprey from the southern Adriatic Sea basin (Petromyzontiformes: Petromyzontidae). 12 records from Erro gen. n. a new genus of featherwing beetles (Coleoptera: Ptiliidae) from Angola and Madagascar. 9 records from A new species of Tambitnotia from Peru, with the first reported female of the genus (Lepidoptera: Tortricidae: Olethreutinae). 1587880 records from Liste des espèces de la faune sauvage (Amphibiens, Mammifères hors Chiroptères, Oiseaux, Orthoptères, Reptiles & Rhopalocères) observées selon le maillage communal français de la base de données naturalistes Faune-France .. 8 records from The neotropical stingless bee genus Nannotrigona Cockerell (Hymenoptera: Apidae: Meliponini): An illustrated key, notes on the types, and designation of lectotypes. 1480 records from Monitoring data of marine turtles on the Togolese coast over 2012-2013 years. 160 records from Ciidae (Coleoptera) records from Britain and Ireland to 2004. 94 records from Range table from benthic foraminifers in ODP Hole 174-1071C. 5 records from A new species of Mada Gordon from the Andes (Coleoptera: Coccinellidae: Epilachnini). 209 records from El complejo Brahea-Erythea (Palmae: Coryphoideae). 180 records from Revision of the family Chasmocarcinidae Serène, 1964 (Crustacea, Brachyura, Goneplacoidea). 2958 records from Phytoplankton abundance in surface water in October 1996, Ilo, Peru. 510 records from Inventaires des cygnes du département de l'Eure. 1 records from New species of the genera Havelockia and Thyone (Echinodermata: Holothuroidea) and first record of T. crassidisca from the southwestern Atlantic Ocean. 23 records from Landwehrbach. 1708 records from Distribution of agglutinated foraminifers in sediment core Well 6407/7-2. 2 records from A new troglobiotic Protaphorura (Collembola, Hexapoda) from the Siberia, Russia. 61 records from Artenvielfalt in der Kinderakademie im RFZ. 46 records from A new species of Microglanis Eigenmann, 1912 (Siluriformes, Pseudopimelodidae) from rio São Francisco basin, Brazil.. 1874 records from Herbario virtual bosques secos de Colombia - Sección herbario TULV (INCIVA). 30 records from Evaluación del riesgo de extinción de setenta y tres especies de lagartijas (Sauria) incluidas en la Norma Oficial Mexicana-059-SEMARNAT-2001. 159186 records from British Antarctic Survey Argos satellite tracking data. 5405 records from Vascular Plant Specimens of Yamagata Prefectural Museum. 2212 records from Avifauna de bosques nublados en la cordillera Occidental, departamentos del Valle del Cauca, Risaralda y sur de Antioquia.. 150 records from Conocimiento de la diversidad y distribución actual del maíz nativo y sus parientes silvestres en México, segunda etapa 2008-2009. 2 records from A new genus of Trichogrammatidae (Hymenoptera: Chalcidoidea) from India. 740 records from Planktic foraminifera assemblage in sediment core GIK17045-3. 798 records from Range table from benthic foraminifers in ODP Hole 172-1054A. 26 records from A review of Synegiodes Swinhoe, 1892 (Lepidoptera: Geometridae), with description of two new species. 1200 records from Growth and age across range extension region of Centrostephanus rodgersii in eastern Tasmania and morphometric comparison of urchins inhabiting kelp versus barrens habitats, Australia (2004-2005). 328 records from Total foraminifera counts of multinet M26/1_MSN844. 1 records from A new record of Potamanthellus caenoides Ulmer 1939 (Ephemeroptera: Neoephemereidae) from the southern Western Ghats of India. 20 records from Osteology and phylogeny of Parioglossus (Teleostei, Gobioidei), with a revised key to the species.. 108 records from Total foraminifera counts of multinet FCA97C_MSN1339. 8 records from Microplankton abundance at bottle station SEPT-1999-K4. 6704 records from University Of Pretoria: Lacewing Database Project (1911-2015). 96 records from Freiheitsring (Frechen). 158 records from Large protozoa abundance measured on concentrated water bottle samples at station PS58/043-4. 3159 records from USAC Mammals Collection. 365 records from Microplankton abundance in the euphotic zone of the Aegean Sea at Station MARCH-94-GN3619940280100500. 4 records from Nesting biology of Paragymnomerus signaticollis tauricus (Kostylev, 1940) (Hymenoptera: Vespidae: Eumeninae). 1 records from Synthèse de la Répartition des populations de bouquetin des alpes en 2005 (réseau Ongulés sauvages ONCFS-FNC-FDC). 2 records from Erythrodiplax ana sp. nov. (Odonata: Libellulidae) from Brazilian palm swamps. 2924 records from Avifauna en dos parches de bosque seco del departamento del Valle Cauca (Colombia). 6924 records from Stone-curlew Annual Surveys. 121 records from Black flies (Diptera: Simuliidae) of Turkish Thrace, with a new record for Turkey. 17 records from Titanogryllus n. gen., the largest Gryllinae cricket from the Neotropical Region with three new species from the Brazilian Atlantic Forest (Orthoptera, Grylloidea, Gryllidae). 10 records from New species of Glossoscolex and Fimoscolex earthworms (Oligochaeta: Glossoscolecidae) from Embrapa Forestry, Paraná, Brazil. 7236 records from The collection of Bathynellacea specimens of MNCN (CSIC) Madrid: microscope slices and DNA extracts. 994 records from (Table 3) Benthic foraminiferal distribution at ODP Site 127-797. 1139 records from Pollen analysis of sediment profile KAIX_A from Kaiserwinkel. 65 records from Porifera Collection - Instituto Nacional de Pesquisas da Amazônia. 1644 records from Phytoplankton abundance in surface water in September 1997, Chimbote, Peru. 531 records from Fish biodiversity of the Vitória-Trindade Seamount Chain, Southwestern Atlantic: an updated database. 114 records from (Table 4) Thecosomata in ODP Hole 134-831A. 53857 records from Naturhistorisches Museum Mainz, Feldbeobachtungsdaten Pflanzen. 8 records from Sächsische Schweiz (Wehlener Gebiet). 52 records from Nano and microzooplankton abundance and biomass at station NBP96-04A-03-16. 1818 records from Distribution of planktic foraminifera of sediment core M33/1_SL_NAST. 15516 records from TPWD HARC Texas Coastal Fisheries Sabine Lake Gill Net. 59 records from DREAL_PACA_-_N2000_-_Pays_Provence_Verte_2017_12_18. 3 records from Tepuidessus grulai sp. nov. from Acopán Tepui in Venezuela (Coleoptera: Dytiscidae: Hydroporinae: Bidessini). 2310 records from Distribution of major planktic foraminifer at Site 177-1093. 52 records from Abundance of epibenthic echinoderms at seafloor photography station POS196_1018. 322 records from Range table from planktonic foraminifers in ODP Hole 180-1115C. 2 records from Taxonomic review of the genus Wasmannia.. 21 records from Diversidad y conservación del germoplasma de henequén Agave fourcroydes Lem. y su posible ancestro silvestre Agave angustifolia Haw.. 835 records from Données naturalistes de Bernard Lalanne-Cassou. 26913 records from Données naturalistes de Franck NOEL. 439 records from PSUZC-Reptile Collection. 83 records from Studies in Liocranidae (Araneae): a new afrotropical genus featuring a synapomorphy for the Cybaeodinae. 3026 records from Fauna de coleópteros lamelicornios del Estado de Michoacán. Primera Fase: Subprovincia neovolcánica tarasca (Cuenca del Lago de Pátzcuaro) 1995-96. 48 records from Review of the Oriental and Palaearctic bee fly genus Euchariomyia Bigot (Diptera: Bombyliidae: Bombyliinae). 343 records from Natura 2000 ZPS Jarny - Mars-la-Tour. 3317 records from BioGIS - Mammals - SPNI. 60 records from New combinations, status, and species of Neotropical Ambrysini (Heteroptera: Naucoridae: Cryphocricinae). 51886 records from Inventaire et suivis d'espèces dans le Parc national des Cévennes. 91329 records from Ministerio de Medio Ambiente, y Medio Rural y Marino. Dirección General de Medio Natural y Política Forestal. Inventario Nacional de Biodiversidad 2007, Invertebrados. 18 records from Assemblage of living benthic foraminifera in sediment core SO117_MC464, 63-125 µm fraction. 67 records from Living benthic foraminifera at station M33/1_MC-03 (NAST), size fraction 30-63 µm. 252 records from Range table from planktonic foraminifers in ODP Hole 180-1115C. 1766676 records from SEWBReC Birds (South East Wales). 331 records from Luderbusch. 3696 records from Heigham Holmes species data held by The National Trust. 50940 records from NOAA National Coral Reef Monitoring Program Benthic Percent Cover. 164 records from Teich im Wald zwischen Böblingen und Schönaich. 596 records from Collections data on ecology of bottom animal of the Southern ocean. 11390 records from SPC PROCFish/C Fish Observations Vanuatu 2003. 493 records from Total foraminifera counts from multinet SO119_MSN1285. 60 records from Resurrecting the genus Enitharoides Brooks, 1953 (Heteroptera: Nepomorpha: Notonectidae): description of three new species and redescription of Enitharoides brasiliensis (Spinola, 1837), comb. nov.. 2598 records from Collection Echinodermata SMF. 238698 records from Isle of Man wildlife records from 01/01/2000 to 13/02/2017. 11868 records from Agroforestry species in Parkia biglobosa's parklands in Northern Benin. 4 records from A new species of large-bodied, tuberculate Hemidactylus Oken (Squamata: Gekkonidae) from the Eastern Ghats, India. 366 records from Malawi-Cicindelidae-Biodiversity-Data. 5885 records from Fish Collection of Yokosuka City Museum. 6 records from Garra sindhi, a new species from the Jebel Samhan Nature Reserve in Oman (Teleostei: Cyprinidae). 12 records from A taxonomic review of the Korean species of the subgenus Datomicra Mulsant & Rey of the genus Atheta Thomson, with description of a new species (Coleoptera, Staphylinidae, Aleocharinae). 313 records from Scleractinia specimens of Kuroshio Biological Research Foundation. 21115 records from Vertebrate Zoology Division - Herpetology, Yale Peabody Museum. 2638 records from MEXU/Flora de Oaxaca. 28 records from Meiofauna abundances at the Arctic Håkon Mosby Mud Volcano (HMMV) of sediment core PS64/323-1. 10794 records from Nonindigenous Aquatic Species (NAS) Database Non-freshwater Specimens. 2840 records from Herbario virtual bosques secos de Colombia - Sección herbario TOLI (UT). 170 records from SNH Invertebrate Site Condition Monitoring 2013/14: Eastern Cairngorms SSSI. 1 records from Description of lithologic section units of IODP Hole 325-M0052C. 4 records from Molecular phylogeny reveals strong biogeographic signal and two new species in a Cape Biodiversity Hotspot endemic mini-radiation, the pygmy geckos (Gekkonidae: Goggia). 40 records from Heavy minerals of sediment core PL94-64. 255684 records from Amphibiens et Reptiles de France (Enquête 2). 3193 records from Inventario de la biota marina (cnidarios, poliquetos, moluscos, crustáceos, equinodermos y peces) del Santuario Islas e Islotes de Bahía Chamela, Jalisco, México. 140 records from SNH Invertebrate Site Condition Monitoring 2015: Blind Moss SSSI. 56 records from Ictiofauna balseana y helmintos parásitos asociados. 247 records from Hemiptera (Heteroptera) collection of National Museum of Nature and Science. 306 records from Plasm bearing foraminifera counts of multinet M42/3_MSN1360. 10 records from Schulinnenhöfe (Gelsenkirchen). 320 records from Wirbach-Taubental (Bad Blankenburg). 1450 records from Données naturalistes d'Alain BERLY. 18752 records from Herps Specimens. 14 records from Nano and microzooplankton abundance and biomass at station NBP97-01-13-5. 29592 records from Insect Collection from the Museu Nacional de História Natural e da Ciência, Universidade de Lisboa, Portugal. 12 records from New species of the leafhopper genera Sophonia and Stenotortor (Hemiptera: Cicadellidae: Evacanthinae) from the Oriental region. 324 records from Range table from benthic foraminifers in ODP Hole 198-1210A. 18 records from Two New Liocranid Species Records From Turkey (Araneae: Liocranidae). 30 records from Hache im Ellernbruch (Sudweyhe / Weyhe). 99 records from Nanoplankton abundance at station GeoB2012-5. 736 records from Ring ouzel national sample survey in the UK in 1999. 2296 records from (Figure 7) Distribution chart of benthic foraminifers in ODP Site 126-793. 111 records from City of Edinburgh Natural Heritage Service - Harperrig Otter Survey. 1698 records from Red-throated diver national surveys in Scotland - raw data. 30 records from Description of two new Calicnemia from Vietnam and central Laos with notes on their congeners in Vietnam (Odonata: Platycnemididae). 749 records from Dorset Invasive Alien Plants - NBN South West Pilot Project Case Studies. 10698 records from Yoann_BLANCHON_2017_12_18. 186 records from Assemblage of living benthic foraminifera in sediment profile GeoB4913-4. 14342 records from Données bibliographiques et opportunistes Mammifères issues du SiRF. 845380 records from Données de la flore d’Alsace (SBA). 4 records from Pipunculidae (Diptera) from southern Iran, including two new species of the genus Tomosvaryella Aczél. 8 records from Description of a new species of Bothynus Hope from Argentina and Bolivia (Coleoptera: Scarabaeidae: Dynastinae). 3 records from Two new Afrotropical genera of Scatopsidae (Diptera). 4371 records from Moluscos de la Colección de Referencia de Biología Marina de la Universidad del Valle (CRM-UV). 123436 records from Données "faune" hors insectes pour le SINP île de France. 10 records from Données naturalistes de Sophie COHEN. 3181892 records from RSPB Big Garden Birdwatch winter sightings in the UK in 2009. 110 records from Microplankton abundance at Station MARCH-1998-GN36199804610MSB03 in the euphotic zone of the Aegean Sea in March 1998. Part 1 - diatoms. 5 records from A new species of Zethus Fabricius (Hymenoptera, Vespidae, Zethinae) from Northeast Brazil, with notes on morphology and distributional records of Z. alessandroi Lopes. 1014 records from Actualización de las bases de datos de colecciones, especies en peligro de extinción, colecta y propagación de germoplasma. 3 records from Medleria gen. nov. adds to the biodiversity of Flatidae (Hemiptera: Fulgoromorpha) in the island of Socotra. 16 records from Búsqueda de poblaciones de la liebre endémica Lepus flavigularis. 3332 records from Composition of the coccolith flora in sediment core GeoB1710-3. 635 records from CG04_2017_12_18. 1470 records from Laubenheimer Bodenheimer Ried - von Stromtalwiesen und Flutrasen. 16 records from Collection Ephemeroptera - SMF. 77 records from Microzooplankton abundance and biomass at station TT045_15-2. 26856 records from Données naturalistes d'Olivier GARGOMINY saisies sous cardObs. 76 records from The Neotropical cuckoo wasp genus Ipsiura Linsenmaier, 1959 (Hymenoptera: Chrysididae): revision of the species occurring in Brazil. 40 records from Inventario de las mariposas diurnas de las cañadas de Morelos y evaluación de factores que permiten el refugio de fauna con limitantes microclimáticas diferentes al macroclima dominante. 259 records from Inventory of the Heteroptera (Insecta: Hemiptera) in Komaba Campus of the University of Tokyo, a highly urbanized area in Japan. 90143 records from Denver Museum of Nature & Science - Entomology. 7 records from The millipede family Paradoxosomatidae in the Philippines, with a description of Eustrongylosoma penevi sp.n., and notes on Anoplodesmus anthracinus Pocock, 1895, recorded in Malaysia and Sri Lanka for the first time (Diplopoda, Polydesmida). 2084 records from Occurrence data of tree species for crystalline Mountain Forest of Tanzania.. 590 records from Estado actual de conservación de liebres y conejos en categoría de riesgo en México. 42 records from (Table 1) Abundance, wet biomass, and carbon biomass of all major groups of phytoplankton in the water column of the Kara Sea. 23084 records from Fish Collection - Instituto Nacional de Pesquisas da Amazônia (INPA). 2498 records from Fishes in MZNA-VERT: anatomy of cyprinids of Spain. PhD project, Rafael Miranda. 21631 records from Database for alien invasive plants occurrences in Germany. 16 records from A new pygmy squid, Idiosepius hallami n. sp. (Cephalopoda: Idiosepiidae) from eastern Australia and elevation of the southern endemic ‘ notoides’ clade to a new genus, Xipholeptos n. gen.. 68 records from A revision of the grunter genus Syncomistes (Teleostei, Terapontidae, Syncomistes) with descriptions of seven new species from the Kimberley region, northwestern Australia. 1158 records from Distribution of calcareous nannofossils from IODP Hole 313-M0027A. 8390 records from Crustacea Collection of Natural History Museum and Institute, Chiba. 5 records from Taxonomy of Euschizomerus Chaudoir 1850 (Coleoptera: Carabidae: Panagaeinae) from India with a new species and new synonym. 2 records from Newly discovered sister lineage sheds light on early ant evolution. 4924 records from Waarneming.nl (NL) - Great Grey Shrike Count 2011-2012. 7759 records from OUPR - Herbário "Professor José Badini". 2 records from Redescription, lectotype designation and new records of Anastrepha luederwaldti Lima (Diptera, Tephritidae). 10 records from Taxonomy and ecology of a new species of Corynura (Hymenoptera: Halictidae: Augochlorini) from Chile and Argentina. 50253 records from National Biodiversity Data Bank. Observation records, 1900-2014. 1477 records from Peces de la cuenca alta y media del río Bita, Vichada (Colombia). 594 records from A taxonomic revision of the Formica rufibarbis Fabricius, 1793 group (Hymenoptera: Formicidae).. 8 records from 20th century Betula pubescens ssp. czerepanovii tree- and forest lines in Norway. 174 records from VFD-H: Heidenrod: Pferdeweide Mürth. 168 records from Total foraminifera counts of multinet M21/4_MSN720. 11776 records from Fortalecimiento de las colecciones de ECOSUR. Primera fase. 124 records from Range table from benthic foraminifers in ODP Hole 172-1059B. 426 records from Données du Centre de la mer de Biarritz. 26 records from UTEP Fish (Arctos). 61 records from Three new taxa of the genus Cechetra Zolotuhin & Ryabov, 2012 (Lepidoptera, Sphingidae) from South-East Asia with notes on other species of the genus. 34 records from Microzooplankton abundance and biomass at station NBP97-08-07-1. 8 records from A review of Gonothrombium Feider, 1950 (Actinotrichida: Microtrombidiidae) with description of a new species from Turkey. 89 records from Phytoplankton abundance at station Sechin_2003-08-27_2, Casma, Peru. 93673 records from Zoologische Staatssammlung Muenchen - International Barcode of Life (iBOL) - Barcode of Life Project Specimen Data. 92 records from Range table from dinoflagellates, acritarchs and prasinophytes in ODP Hole 160-969A. 40793 records from FLOR - Herbário do Departamento de Botânica da Universidade Federal de Santa Catarina. 2 records from A new species of Anthiadinae (Teleostei: Serranidae) from São Pedro and São Paulo Archipelago, Brazil, Equatorial Atlantic.. 936 records from Alterra (NL) - Microarthropods inventory in Dune vegetation. 3913 records from (Table T3) Calcareous nannofossil stratigraphy of ODP Hole 198-1208A. 67 records from Einen Tag lang Forscher sein - Die 5c der Erich-Kästner-Schule erforscht das Bachemer Wiesental. 4 records from Pseudolycoriella skusei sp. nov. (Diptera: Sciaridae), a new dark-winged fungus gnat from Norfolk Island and Australia. 3850 records from (Table S2a) Nannofossil species richness in the Bass River section. 2220 records from (Appendix) Foraminifer abundance of a volcaniclastic interval from ODP Hole 197-1206A. 454 records from Data on cetacean strandings (1999 - 2014) on the Ukrainian coast of the Black Sea and the Sea of Azov and adjoining areas. 1 records from Two deep-sea decapod crustaceans collected off eastern Hokkaido, Japan: Sclerocrangon rex n. sp. (Caridea: Crangonidae) and Munidopsis verrilli Benedict, 1902 (Anomura: Munidopsidae). 466 records from Borstgrasrasen um die Burg Baldenau im Oberen Dhrontal. 2282 records from Registros Primates Neotropicales Convocatoria APC. 11692 records from Benthic foraminifera distribution of sediment core GIK17957-2. 10 records from Review of the genus Promalactis Meyrick, 1908 (Lepidoptera: Oecophoridae) III. The trilineata species group, with descriptions of four new species. 1 records from Off the scale: a new species of fishscale gecko (Squamata: Gekkonidae: Geckolepis) with exceptionally large scales. 9471 records from Mollusques dulcicoles de France - Jacques MOUTHON. 602 records from Molluscan specimens from the Astrolabe Reefs (Kadavu, Fiji), 1986-2006. 100 records from Antractic whale observation on a platform of opportunity abroad krill fishing vessel "Dalmor II", April - July 2011.. 43 records from Bases de datos de plantas, insectos, reptiles, anfibios, aves y mamíferos del “Arroyo la Junta, Una joya de biodiversidad en la Reserva de la Biosfera Sierra La Laguna”. 134 records from Planktic foraminifera counts at CTD station PS55/079-1. 947 records from Relative abundance of Neogene nannofossils at ODP Site 138-844 from the eastern equatorial Pacific. 75 records from Foraminifera species abundances from tow TT007_15-MOC23. 90 records from The freshwater shrimp family Euryrhynchidae Holthuis, 1950 (Crustacea: Decapoda: Caridea) revisited, with a taxonomic revision of the genus Euryrhynchus Miers, 1878. 72 records from Schulgelände Lise Meitner Realschule (Paderborn). 222 records from Birdrace-Uhulogen-Lippe. 299 records from Collection Aves (bird skins) SMF. 1080 records from Nematode abundance in sediments obtained during RRS Discovery cruise D297. 26 records from A new Bifidocoelotes species, with the description of the male of B. primus from Hong Kong, China (Agelenidae: Coelotinae). 1805 records from La familia Asclepiadaceae en México. 1049 records from Computarización de la Colección de helmintos parásitos de peces del estado de Tabasco. 1 records from Revision of the genus Nybelinella (Teleostei, Bythitidae) with a new Atlantic, abyssal species. 18 records from DNA barcoding and morphological studies confirm the occurrence of three Atarbolana (Crustacea: Isopoda: Cirolanidae) species along the coastal zone of the Persian Gulf and Gulf of Oman. 29 records from Morphological examination and phylogenetic analysis clarify the taxonomic status of Cuban Longior Travassos & Kloss, 1958 (Nematoda: Thelastomatoidea: Hystrignathidae). 166 records from Birdrace-Die_Vogelscheuchen-Herford. 272 records from Birdrace-SpeedBirder-Zwickauer_Land. 740 records from Otter survey of Ireland 2004 & 2005. 2 records from Description of a new species of Liocheles Sundevall, 1833 (Hormuridae) from India. 15108 records from JOI - Herbário Joinvillea. 1 records from A new cryptic rock-dwelling Hemidactylus Oken, 1817 (Squamata: Gekkonidae) from northern Karnataka, India. 7 records from Microplankton counts and carbon biomass at station TT007_9-CTD108. 2066 records from Deep-water azooxanthellate Scleractinia from Vanuatu, and Wallis and Futuna Islands. 168 records from BIRDRACE Vogelscheuchen. 12494 records from Census of medical plant species of Benin (West Africa) by SOS Biodiversity. 88 records from A review of Smicronyx Schoenherr (Coleoptera, Curculionidae) of Israel, with description of two new species. 20 records from Four new species of the subgenus Pachylaelaps (Longipachylaelaps) from Italy, with a new identification key to the known species (Acari: Pachylaelapidae). 133 records from Phytoplankton abundance measured in surface water during Charles Darwin cruise CD85. 12656 records from (Table T7) Calcareous nannofossil stratigraphy of ODP Hole 198-1210B. 162 records from Birdrace-Die_Ornithomaten-Herford. 5 records from First record of the millipede genus Nesorthomorpha Jeekel, 1980 in Vietnam with description of a new species (Diplopoda, Polydesmida, Paradoxosomatidae). 111099 records from Suivi Temporel des Rhopalocères de France (STERF). 61680 records from NINA Vanndata fisk. 430 records from Total foraminifera counts of multinet POS247/2_MSN1386. 87 records from Données 2015 de l'Observatoire de la Biodiversité des Forêts. 117 records from Range table from benthic foraminifers in ODP Hole 172-1059A. 135 records from California State University, Long Beach Mammals. 273 records from Total foraminifera counts from multinet SO119_MSN1303. 4 records from A new species of inseminating seasonal killifish of the Cynopoecilus melanotaenia complex from southern Brazil (Cyprinodontiformes: Rivulidae). 22 records from Revisions of Australian ground-hunting spiders. V. A new lycosoid genus from eastern Australia (Araneae: Tengellidae). 5518 records from Données de mammifères enregistrées dans BazNat - Lot 2. 1584 records from Ostracoda in sediment core PS51/154-11. 184 records from Nottekanal, Klasse 7 - 10. 90 records from Taxonomic review of the moth family Thyatiridae (Lepidoptera) from Yunnan province, China. 132 records from A review of the Cyana bianca (Walker, 1856) species-group with descriptions of a new species and a new subspecies from Indochina (Lepidoptera, Erebidae, Arctiinae). 58 records from Waldwiese. 1 records from A new species of Plestiodon (Squamata: Scincidae) from the Balsas Basin, Mexico. 182 records from Planktic foraminifera counts at CTD station M39/4_361CTD-18. 3401 records from Clare Biological Records Centre Dataset 2004-2007. 235 records from Expédition Karubenthos 2012 : données issues des publications. 9 records from The identity of the Carsidara species (Hemiptera: Psylloidea: Carsidaridae) associated with Firmiana simplex (Malvaceae) in Japan and Korea. 234 records from Plasm bearing foraminifera counts of multinet POS247/2_MSN1389. 920 records from Inventario florístico en Baja California Sur: Región del Cabo e Islas adyacentes. 2074 records from Diatom assamblage in samples from sediment trap OG5. 5 records from Pseudomystus stenogrammus, a new species of bagrid catfish from Borneo (Teleostei, Bagridae).. 8 records from A review of the Oriental leafhopper genera Thampoa Mahmood and Guheswaria Thapa (Hemiptera: Cicadellidae: Typhlocybinae). 4 records from A new species of the genus Rhinoleucophenga (Diptera: Drosophilidae) and redescription of five species from Neotropical region. 982 records from Tasmanian Museum and Art Gallery provider for OZCAM-Arthropoda. 20037 records from Données issues du dispositif de Biosurveillance des Retombées Atmosphériques Métalliques par les Mousses (BRAMM). 4 records from A new species of Eidmanacris Chopard, 1956, with notes on its distribution in Brazilian caves (Phalangopsidae, Luzarinae). 174 records from Nematode abundances in sediments from the Håkon Mosby Mud Volcano (HMMV) obtained during expeditions with Polarstern and Pourquoi Pas?. 50 records from Flora und Fauna im Brexbachtal. 1173390 records from MICROBIS database. 10 records from The bark louse family Stenopsocidae (Psocodea: Psocomorpha) newly recorded from Laos, with description of three new species. 191 records from Herpetofauna laguna El Tinije. 246 records from Birdrace-Professorenteam-Münster. 121 records from Species diversity of fiddler crabs, genus Uca Leach, 1814 (Crustacea: Ocypodidae), from Taiwan and adjacent islands, with notes on the Japanese species. 6927 records from Estudios bióticos (Plantas, Fauna Edáfica, Anfibios y Aves) en los Complejos de páramos las Hermosas y Chilí-Barragán.. 3345 records from Colección de Mamíferos del Instituto de Ciencias Naturales (ICN-MHN-Ma). 1 records from On the taxonomy of Lygosoma bampfyldei Bartlett, 1895 (Squamata: Scincidae) with descriptions of new species from Borneo and Peninsular Malaysia and the resurrection of Lygosoma schneideri Werner, 1900. 664 records from Vegetación de sistemas cársticos en el municipio de El Peñón, Santander - Proyecto Colombia BIO. 459266 records from Swiss National Orthoptera Databank. 1 records from Two new earthworm species (Oligochaeta: Annelida) of the Orinoquia region of Colombia. 516 records from Données naturalistes de Laurent KREMMER. 131 records from Planktic foraminifera counts at CTD station PS55/083-1. 41 records from Biological Collection, National Institute of Oceanography, Goa, India. 44485 records from The Environmental Sample Collection of Spiders at the Staatliches Museum für Naturkunde Karlsruhe. 30091 records from BIOWIDE eDNA Fungi dataset. 41 records from Occurrence data set for wild food plant species in Zimbabwe's biodiversity hotspots. 297 records from Steinbruch Mainz-Weisenau. 270 records from ABC_Useful Plants of Malawi: Species used as Herbal aphrodisiacs. 1288 records from Palynological analysis of sediment core GeoB3910-2. 33 records from Computarización del Herbario ENCB. Fase I (Base de datos de los ejemplares del Valle de México). 343 records from Total foraminifera counts of multinet M12/3_MSN557. 2607 records from (Table T5) Planktonic foraminifera stratigraphy of ODP Hole 198-1209A, Zones P9-P11. 3755 records from Fauna y flora del municipio de Lipa, Arauca. 2 records from A new species of Crematogaster from the pinelands of the southeastern United States.. 153 records from Plasm bearing foraminifera counts from multinet SO119_MSN1285. 32 records from Review of the leafhopper genus Alnetoidia Dlabola (Hemiptera: Cicadellidae: Typhlocybinae: Erythroneurini) from China, with descriptions of two new species. 62 records from Nationalpark Harz Schul-AG Braunlage. 26900 records from Israeli Butterfly Monitoring Scheme (BMS-IL). 516 records from Planktic foraminifera distribution of sediment core GIK17940-2. 33 records from Polychaeta abundance in surface sediments of the east Greenland continental slope (2000m section). 1847 records from (Table T3) Planktonic foraminiferal stratigraphy of ODP Hole 173-1068A sediments. 140 records from Inventaire de la faune aviaire et de l'Ichtyofaune de la mare de l'Abarkaizé et des Oiseaux de Dan Saga. 140 records from Review of the Neotropical spider wasp subgenus Anoplius (Dicranoplius) Haupt (Hymenoptera: Pompilidae), new comb.. 3521 records from Fish: Records for Kent.. 76 records from Was lebt in der Brutzwiese?. 112 records from Phytoplankton abundance at station Sechin_2003-07-15_2, Casma, Peru. 26 records from Biodiversity Surveys, South-east Arnhem Land. 517 records from Ichthyofauna of the Kubo, Tochikura, and Ichinono river systems (Kitakami River drainage, northern Japan), with a comparison of predicted and surveyed species richness. 45 records from Illustrated and online catalog of type specimens of freshwater fishes in the Colección de Peces Dulceacuícolas of Instituto de Investigación de Recursos Biológicos Alexander von Humboldt (IAvH-P), Colombia. 35 records from Benthic macrofauna abundance of sediment core 13200-045. 2284 records from Monitoreo de la población de la guacamaya verde en la Reserva de la Biosfera Tehuacán-Cuicatlán. 1054 records from Aves de la cuenca alta y media del río Bita, (Vichada) Colombia. 86 records from Données naturalistes de Pierre-Alexis RAULT. 124179 records from The Fungal Collection at the Senckenberg Museum für Naturkunde Görlitz. 4 records from Two new Isotomidae species (Collembola) from Espírito Santo State, Brazil. 18 records from Taxonomic status of maskrays of the Neotrygon kuhlii species complex (Myliobatoidei: Dasyatidae) with the description of three new species from the Indo-West Pacific. 216139 records from USGS Patuxent Wildlife Research Center Seabirds Compendium. 2411 records from (App 8) Relative contents of planktonic foraminifera species in sediments from Core GeoB3011-2. 1 records from The Cat-eyed Snakes of Madagascar: Phylogeny and Description of a New Species of Madagascarophis (Serpentes: Lamprophiidae) from the Tsingy of Ankarana. 28 records from Halophila stipulacea in the Caribbean Sea. 1 records from Annotated catalogue of the click-beetle subfamily Tetralobinae (Coleoptera: Elateridae). 8 records from A new species of the fangblenny Adelotremus from Indonesia, with supplemental description of A. leptus (Teleostei: Blenniidae: Nemophini). 9 records from Museu Paraense Emílio Goeldi - Acanthocephala Collection. 5 records from Microplankton abundance in the euphotic zone of the Aegean Sea at Station SEPT-1998-MNB5. 3 records from Freies Projekt Speichersdorf - Region Oberfranken. 44 records from Bachabschnitt der Nette (Osnabrück). 59 records from Microzooplankton abundance and biomass at station TT043_4-1. 182598 records from Données photographiques validées de la galerie du forum "Le Monde des Insectes". 173 records from (Fig. 4) Nannofossil abundance of Cretaceous profile Pré-Guittard, SE France. 466 records from Species occurring in the mytilid and alvinellid communities within the 9°N hydrothermal field at the East Pacific Rise. 1 records from Teretamon spelaeum, a new species of freshwater crab (Crustacea: Decapoda: Potamidae) from a limestone cave in Meghalaya, India. 476 records from BIRDRACE Gätkes Erben. 6 records from Revision of the Zethus luzonensis species-group (Hymenoptera: Vespidae: Eumeninae), with description of a new species. 12 records from Ontogeny as an important part of integrative taxonomy in tergipedid aeolidaceans (Gastropoda: Nudibranchia) with a description of a new genus and species from the Barents Sea. 9283 records from The cryptogamy collection (PC) at the Herbarium of the Muséum national d'Histoire Naturelle (MNHN - Paris). 608 records from Total foraminifera counts of multinet M21/1_MSN608. 56 records from There and back again: More on the taxonomy of the crab spiders genus Epicadus (Thomisidae: Stephanopinae). 182 records from A taxonomic review of the genus Antepipona de Saussure, 1855 (Hymenoptera: Vespidae: Eumeninae) from India. 2394 records from Actualización y depuración de las bases de datos de la Colección Nacional de Helmintos: P085 y Q028. 750 records from Carabidae of the European North-East of Russia. 206 records from BIRDRACE federleser. 6937 records from Análisis de los efectos ecológicos del aprovechamiento forestal en el Corredor Biológico Mesoamericano: mamíferos, plantas y sus interacciones. 4560 records from Consolidación de la colección de referencia de peces de la Estación Mazatlán, (ICMyL-UNAM) e implementación de los mecanismos para su manejo y consulta. 1297 records from Recensement et distribution Mammifères marins Guadeloupe Antilles françaises (AET). 199 records from (Table 4) Ostracoda abundances in sediment core PS2212-3 (Yermak Plateau). 4 records from Taxonomy of Litoria graminea (Anura: Hylidae), with descriptions of two closely related new species. 524 records from Variability of benthic Foraminifera north and south of the Denmark Strait. 79930 records from CAS Botany (BOT). 2 records from Dolichocephala Macquart of Thailand (Diptera: Empididae: Clinocerinae). 33 records from Abundance and carbon biomass of phytoplankton at station TT012_5-CTD63. 1602 records from Palynological analysis of sediment core GeoB9508-5. 210 records from Plasm bearing foraminifera counts from M35/1_MSN1059. 634 records from The Myriapoda & Onychophora collection (MY) of the Muséum national d'Histoire naturelle (MNHN - Paris). 54 records from New data on the Syrphidae (Diptera) of Iran, with descriptions of two new species. 176 records from (Table 1) Abundance of live benthic foraminifera in surface sediments of the Arctic Ocean. 1 records from A revision of the Neotropical ant-like genus Cardiacephala Macquart, including Plocoscelus Enderlein syn. nov. (Diptera: Micropezidae, Taeniapterinae). 1016 records from Barents Sea Zooplankton – March and May 1998 and July 1999. Zooplankton sampling on board the Norwegian R/V Jan Mayen, program ALV. 11796 records from ARC-PPRI: National Collection of Nematodes and South African Plant-Parasitic Nematode Survey(1901-2014). 227 records from Range table from benthic foraminifers in ODP Hole 198-1207B. 4 records from Taxonomic contributions to Ageniella Banks, 1912 (Hymenoptera: Pompilidae) from Brazil. 785 records from Flux data of NU2_trap (Table A1). 4 records from New and poorly known Meligethes Stephens from China, with bionomical data on some species (Coleoptera: Nitidulidae: Meligethinae). 740 records from (Table 3d) Foraminiferal distribution chart of petroleum well Great-Eastern-1. 234 records from Centre d'Estudis Avançats de Blanes. Macròfits Pirineu. 25875 records from Données de Mammifères enregistrées dans BazNat - Lot 1. 5721 records from Wikiplantbase #Sicilia. 96 records from Abundance of non-diatom phytoplankton measured on water bottle samples at station PS58/009-2. 1451 records from Conocimiento de la diversidad y distribución actual del maíz nativo y sus parientes silvestres en México, segunda etapa 2008-2009. 4 records from Two new species of Rhopalopsole (Plecoptera: Leuctridae) from China. 30 records from Abundance, biovolume and biomass of heterotrophic dinoflagellates at station TT011_3-CTD39. 5 records from Begonia henrilaportei Scherber. & J. Duruisseau (Begoniaceae), a new endemic species from the Masoala peninsula, Madagascar. 115 records from Foraminifera and stable isotopes of sediment core PS2076-1. 996 records from Bekkelag basin, Inner Oslofjord. 215 records from Naturpark Kottenforst-Ville Sammelaktion 15.-19.6.. 8134 records from Distribution of major planktic foraminifer at Site 177-1090. 644 records from Estudio herpetofaunístico de la Sierra Mazateca, Oaxaca, México. 46 records from Estudio taxonómico del género Quercus (Fagaceae) en el Estado de México. 16 records from Cordulegaster virginiae sp. nov. from Mexico, including a comparison with C. diadema Selys, 1868, and a redescription of its larva (Odonata: Cordulegastridae). 1 records from A new species of Notosacantha Chevrolat (Coleoptera: Chrysomelidae: Cassidinae) from Timor-Leste with a key to the Notosacantha vicaria - group. 34 records from Phytoplankton abundance in surface water in 1994, Ancon, Peru. 4485 records from Lower Albian LArboudeysse (Niveau Paquier) range chart in percentages of nannofossils, in SE France. 282 records from Plasm bearing foraminifera counts from multinet SO119_MSN1284. 51948 records from Long-term Bird Census in Cigu 2004-2017. 28 records from Three new species of Alburnoides from the southern Black Sea basin (Teleostei: Cyprinidae). 1397 records from Abundance of living coccolithophores in the northern Arabian Sea (Table 2). 1502 records from CNIN/Tipos Coleoptera. 4 records from Range table from planktonic foraminifers in ODP Hole 159-960A. 246 records from BARTH-Environnement_2017_12_18. 269 records from Range table from benthic foraminifers in ODP Hole 210-1276A. 4 records from Schistura epixenos, a new species of loach from the Nakai Plateau, Laos (Teleostei: Nemacheilidae). 30 records from Four new species of the genus Trachelas L. Koch, 1872 and the first record of T. vulcani Simon, 1896 from South-West China (Araneae: Trachelidae). 175 records from Microzooplankton abundance measured on water bottle samples at station PS65/514-2. 666 records from Assemblage of dinoflagellate cysts analysed in surface sediment samples off Peru. 26 records from Four new species and one new subspecies of Arctiinae (Lepidoptera: Erebidae) from the Tambopata river, Madre de Dios, Peru. 44 records from Additional new species of the genus Obolopteryx Cohn et al. 2014 (Ensifera: Tettigoniidae) from Northeastern Mexico. 327 records from Plasm bearing foraminifera counts of multinet M36/6_MSN1193. 24 records from SNH Invertebrate Site Condition Monitoring 2013/14: Dollar Glen SSSI. 168 records from New records of sabellids and serpulids (Polychaeta: Sabellidae, Serpulidae) from the Tropical Eastern Pacific. 482 records from Total foraminifera counts of multinet M21/2_MSN658. 10476 records from SANBI: DNA Banking(1987-2011). 1088 records from (Appendix A1) Calcareous nannofossil counts of ODP Site 207-1258. 27603 records from The national database for marine data (MADS). 1591 records from Naturalis Biodiversity Center (NL) - Mammalia. 59 records from Microzooplankton abundance and biomass at station TT043_11-1. 19 records from Description of lithologic section units of IODP Hole 325-M0035A. 4 records from Taxonomy of deep-water tetillid sponges (Porifera, Demospongiae, Spirophorina) from Brazil, with description of three new species and new characters. 1 records from A new Limnonectes (Anura: Dicroglossidae) from southern Laos. 8 records from Revision of the Agrilus wittemani species - group (Coleoptera: Buprestidae: Agrilini) with description of three new species from India and Myanmar. 202 records from BIRDRACE Enger am Spektiv. 219 records from Ghent university - Zoology Museum - Nematod Collection. 288 records from Size of planktic foraminifera at CTD station M39/4_402CTD-55. 398 records from Total foraminifera counts from multinet M32/3_MSN956. 163 records from Assemblage of living benthic foraminifera in sediment core SO118_MC-52, 63-125 µm fraction. 17 records from A stonefly species extinct in Europe (Taeniopteryx araneoides Klapalek, 1902, Taeniopterygidae, Plecoptera) is thriving in the Irtysh River in West Siberia and North Kazakhstan. 18510 records from Données naturalistes de Julien BIRARD [Inventaire Eclair 18 juin]. 117 records from Range table from benthic foraminifers in ODP Hole 172-1060A. 6 records from A new spider species, Heser stoevi sp. nov., from Turkmenistan (Araneae: Gnaphosidae). 26 records from Warnowufer Groß Klein. 14 records from Stadtrandlandschaft Apolda-Nord. 30 records from Microzooplankton abundance and biomass at station NBP97-03-13-2. 9 records from A new species of Podocinum (Acari: Podocinidae) from Brazil, and supplementary descriptions of three species of this genus. 160 records from Echinoderms occurence in a strongly contaminated Bay (Portman, Spain), using ROV and Scuba-diving surveys. 429 records from (Table 4) Distribution of calcareous nannofossils at ODP Hole 125-785A. 480 records from Sistemática e historia natural de algunos anfibios y reptiles de México. 5 records from A new species of Choroterpes Eaton, 1881 (Ephemeroptera: Leptophlebiidae) from India. 11335 records from Diversidad de ocho grupos de insecta (Odonata, Lycidae, Phengodidae, Lampyridae, Cantharidae, Cerambycidae, Syrphidae y Vespidae) en tres regiones con bosque tropical caducifolio en México. 44051 records from Alterra (NL) - Entomofauna inventory in peat swamps. 238 records from Evaluación del ámbito hogareño y calidad de hábitat del borrego cimarrón (Ovis canadensis mexicana), Berrendo sonorense (Antilocarpa americana sonoriensis) y del Puma (Felis concolor) en la Reserva de la Biósfera El Pinacate y Gran Desierto de Altar. 6264 records from (Table 2) Occurrence of Late Cretaceous foraminifers and radiolarians in ODP Hole 130-807C. 644386 records from Florida Keys Reef Visual Census 2010. 5608 records from Museu de Ciències Naturals de Barcelona: MCNB-Malac. 38 records from Nano and microzooplankton abundance and biomass at station NBP96-04A-11-5. 2962 records from Leicestershire and Rutland Mature trees Inventory 2011. 334 records from Pollen data of trap CB4. 10 records from A revision of the genus Anadenosternum Athias-Henriot (Acari: Mesostigmata: Parasitidae). 11 records from Results of foraminifer and ostracode analyses of the Neogene of Hole 302-M0004C. 459 records from annex1. 394 records from Total foraminifera counts of multinet POS247/2_MSN1377. 4726 records from Sutton Hoo species data held by The National Trust. 8 records from Review of Allanagrus Noyes & Valentine (Hymenoptera: Mymaridae) with a key to species. 106 records from Rare vascular plant species in North-West of Kostroma region, Russia. 200 records from Assemblage of living benthic foraminifera in sediment core GeoB3706-3. 66 records from (Table 3) Sr-Nd-Pb isotope ratios of selected Cocos Plate samples. 10 records from Gynacantha dryadula sp. nov. from the Guiana Shield (Odonata, Anisoptera: Aeshnidae). 282 records from Draubiotop Lavamünd. 102 records from Phytoplankton abundance at station Rigel_5_2005-02 in Febraury 2005, Chipana, Chile. 8 records from Taxonomy of the genus Pristidia Deeleman-Reinhold, 2001 (Araneae: Clubionidae) in China. 290 records from Large protozoan and small metazoan abundance measured on concentrated water bottle samples at station PS65/593-14. 136 records from Abundance of planktic foraminifera at CTD station PS55/080-1. 323 records from Foraminifera species abundances from tow TT011_12-MOC74. 577 records from "Schwarzwassertal" bei Pobershau. 110 records from Phytoplankton abundance in the Wadden Sea off List, Sylt, North Sea in 2008. 619 records from Planktic foraminifera assemblage in sediment core GIK23419-8. 31 records from A synopsis of the subgenus Centris (Hemisiella) Moure, 1945 (Hymenoptera: Apidae: Centridini) in Colombia, with description of a new species. 1853 records from Zoological Museum Amsterdam, University of Amsterdam (NL) - Diptera_Tipulidae_Palearctic. 3406 records from Plan de vertebrados de la Patagonia. 184 records from Birdrace_TerraCamper-Münster. 252 records from Revision of Archaeoteleia Masner (Hymenoptera: Platygastroidea, Scelionidae).. 12625 records from Distribution of planktic foraminifera of sediment core M35003-4. 19 records from Range table from planktonic foraminifers in ODP Hole 180-1109C. 6 records from Description of lithologic section units of IODP Hole 325-M0054B. 10 records from New species, genera, families, and range extensions of freshwater bryozoans in Brazil: the tip of the iceberg?. 3051 records from AlgaTerra. 1315 records from Records from the South Australian Seed Conservation Centre. 76 records from (Table T2) Dinoflagellate cysts and pollen/spore yield and preservation in ODP Site 188-1166. 304538 records from Données acquises dans le cadre de l'activité du bureau d'étude BIOTOPE (1994 - 2013). 166 records from Range table from planktonic foraminifers in ODP Hole 167-1011C. 860 records from Molluscs in surface sediments off Sylt collected during HEINCKE cruise HE272. 27 records from Endophallus structure: a promising tool for cryptic species identification in Timarcha Samouelle, 1819 (Coleoptera: Chrysomelidae: Chrysomelinae). 2057 records from Danielsberg (Mölltal, Kärnten). 34 records from Vegetación vascular terrestre, entomofauna y macrofauna de la Isla Cayo Serrana durante la Expedición Seaflower 2016 - Proyecto Colombia BIO. 16977 records from LPO_PACA_2017_12_18. 478 records from Bulk components and planktonic foraminifera of sediment core GeoB3302-1. 206 records from Living Prairie Museum Manitoba Herbarium (LPMMBH). 16 records from The Elachistidae (Lepidoptera: Gelechioidea) of Caucasus, with description of three new species. 68 records from Borkhart. 580 records from Planktic foraminifera assemblage in sediment core GIK17730-4. 2249 records from HSU Vertebrate Museum Mammals Collection. 560 records from Targeting a portion of central European spider diversity for permanent preservation. 3459 records from Centre for Biodiversity Genomics (BIOUG) - Marine Invertebrates. 8 records from Two new species of Miltochrista from India (Lepidoptera, Erebidae, Arctiinae). 11463 records from Liste des pays par taxon spécimen TOGO. 21650 records from Census of species recorded during phytosociological surveys in Benin. 2788 records from NRW Regional Data: all taxa (sensitive species only), West Wales. 413 records from Pollen analysis of sediment profile KAI2 from Kaiserwinkel. 6377 records from Computarización de la Colección de mamíferos del Centro de Investigaciones Biológicas del Noroeste SC. 4 records from New records of Panchaetothripinae from Japan (Thysanoptera, Thripidae). 4 records from The genus Pseumenes Giordani Soika, 1935 (Hymenoptera: Vespidae: Eumeninae) in the Philippine Islands, with description of a new species. 197 records from Rutilans. 76 records from SNH Invertebrate Site Condition Monitoring 2015: Lurgie Loch SSSI. 188 records from UTEP Insects (Arctos). 25 records from Review of Cosmocomoidea (Hymenoptera: Mymaridae) from China, with descriptions of two new species. 8344 records from (Appendix 2) Distribution of generalized biologic, anthropogenic, and volcanic constituents in sediment samples collected between 1995 and 2010 in the San Francisco Bay coastal system. 1252 records from GNOR-Projekt "Halbwilde Weidehaltung zwischen Kamp-Bornhofen und Kestert" und Umland. 18090 records from Leicestershire Bryophyte Data. 484 records from Landschaftspflegehof (Berlin). 20 records from Bachpatenschaft Beeke. 168 records from BIRDRACE Hasenclevers Erben - NaBu-Bi-BirdRace-Open. 18 records from Range table from dinoflagellates, acritarchs and prasinophytes in ODP Hole 159-960A. 24662 records from TPWD HARC Texas Coastal Fisheries Upper Laguna Madre Gill Net. 354 records from SPC CoFish Invertebrates Observations Niue 2005. 252 records from Total foraminifera counts from M35/1_MSN1051. 3028 records from Gemeinde Sursee. 10732 records from City of Edinburgh Natural Heritage Service - Bavelaw Marsh Bird Hide Records. 390 records from (Fig. 8g-h, 11) Abundance of planktonic foraminifera and estimation of sea surface temperature and export production of sediment core MD95-2040. 261 records from Assemblage of living benthic foraminifera in sediment core SO118_MC-43, 30-63 µm fraction. 1592 records from Relative abundance of benthic foraminifera in sediment core SO90-137KA. 1506 records from Insect specimens of Omogo Mountain Museum. 852 records from OMMAG_Suivi_Dauphins_Les_Saintes. 76 records from Review of the genus Eopompilus Gussakovskij, 1932 (Hymenoptera: Pompilidae) with the description of new species from China. 508 records from Spatial repartition of Antiaris toxicaria Lesch., Ceiba pentandra (L) Gaert, Terminalia superba Engl. & Diels and Triplochyton scleroxylon K. Schum. in Niaouli, Bonou, Pobe forests (South-Benin). 334 records from Artenvielfalt auf den Elbwiesen (Dessau). 1009 records from Données naturalistes de Daniel PAVON. 632 records from GBIF: Nova Scotia Museum of Natural History - Freshwater mussels. 72 records from Taxonomic revision of the Afrotropical species of Pachyanthidium Friese (Hymenoptera: Megachilidae: Anthidiini). 1752 records from Database on reference specimens for medicinal plants of the Rubiaceae family, conserved at the CNARP herbarium. 2 records from Vigna yadavii (Leguminosae: Papilionoideae), a new species from Western Ghats, India. 10 records from A new genus and species within the tribe Earomyiini (Diptera, Lonchaeidae). 199 records from Flora y fauna asociada al hábitat del Manatí antillano en la Ciénaga de Paredes, Magdalena Medio Santandereano. 198 records from Microplankton abundance at Station MARCH-1997-GN36199704601MSB06 in the euphotic zone of the Aegean Sea in spring 1997. Part 2 - dinoflagellates. 571 records from Total foraminifera counts of multinet M21/1_MSN606. 152 records from Inventario de Mamíferos Mámbita. 2 records from A new morphologically cryptic species of Phyllomedusa (Anura: Phyllomedusidae) from Amazonian forests of northern Peru revealed by DNA sequences. 48 records from Canadian Museum of Nature Mammal Collection. 42 records from Microzooplankton abundance and biomass at station NBP97-08-25-4. 34 records from Feuchtwiese am Nationalpark-Haus Neuwerk. 28 records from New and little known species of Halolaelaps (Acari: Mesostigmata: Halolaelapidae) from Ukraine. 303658 records from Estonian Nature Observations Database. 189 records from Naturpark Sternberger Seenland. 50422 records from Botanical Museum, Copenhagen, Mycology Herbarium. 106191 records from Biodiversitätsdatenbank des Landes Salzburg. 5170 records from NCSM Mammals Collection. 91 records from Heard Island Shag Phalacrocorax nivalis census, Heard Island 1992. 172 records from Microzooplankton abundance measured on water bottle samples at station PS65/546-2. 22 records from Taxonomy of Paraplatyarthrus Javidkar and King (Isopoda: Oniscidea: Paraplatyarthridae) with description of five new species from Western Australia, and comments on Australian Trichorhina Budde-Lunde, 1908 (Platyarthridae). 3959 records from Aves del Parque Nacional Cumbres de Monterrey, Nuevo León, México. 900 records from DMNS Parasite Collection (Arctos). 182 records from GEO-Tag mit der NAJU des Landkreises Ahrweiler am Bausenberg. 379 records from Microplankton abundance in the euphotic zone of the Aegean Sea in winter 1995. 9 records from Biology and population studies of two endemic orchid species on sub-Antarctic Macquarie Island. 6 records from Studies on the genus Aeolothrips (Thysanoptera: Aeolothripidae) in Iran, with a key to species. 4698 records from Estudio taxonómico y zoogeográfico de áreas selectas de peces marinos en Laguna Madre y Costas de Tamaulipas, Veracruz y Campeche, México. 1620 records from Phytoplankton abundance during HYDROMET cruise Hydromet90/4. 310 records from Revisión de la subfamilia Asopinae (Hemiptera-Heteroptera-Pentatomidae) para México. 31888 records from Colección general del plantas vasculares del Herbario JBB. 2188 records from Données naturalistes de Matthias COLIN. 5 records from Draposa, a new wolf spider genus from South and Southeast Asia (Araneae: Lycosidae). 146478 records from Colección de Entomología del Instituto Alexander von Humboldt. 15 records from Taxonomic note on the oil-collecting bee Centris dimidiata (Olivier, 1789) (Hymenoptera: Apidae: Centridini). 328270 records from Species data for Scottish waters held and managed by Scottish Natural Heritage, derived from benthic surveys 1993 to 2014. 27 records from The subspecific structure of Dorcadion (Cribridorcadion) pusillum Küster (Coleoptera: Cerambycidae) with description of two new subspecies from Romania. 250 records from Cowan Tetrapod Collection - Herpetology. 503 records from Total foraminifera counts from multinet M31/3_MSN898. 263749 records from CSIC-Real Jardín Botánico-Colección de Plantas Vasculares (MA). 12454 records from SPC NECTALIS Zooplankton/Micronekton specimens, New Caledonia 2014. 230 records from Plasm bearing foraminifera counts of multinet M36/2_MSN1107. 10 records from Upper Silesian Museum, Bird Collection. 333 records from Phytoplankton abundance at station CD46_0705C#4. 520 records from Abundance of empty diatom frustules measured on water bottle samples at station PS58/049-3. 6 records from Planktic foraminifera counts of multinet PS2616-5. 21 records from (Table 2) Abundance of benthic foraminifers of sediment core PS2445-2. 8414 records from CASES2003_2004. 105 records from Digitalización y sistematización de las colecciones biológicas del INECOL. 9 records from Données additionnelles d'Echasse blanche Himantopus himantopus 1980-1991 nicheuse probable ou certaine (hors période atlas 1985-1989). 2 records from A review of the genus Syrianarpia Leraut (Crambidae: Scopariinae) with description of S. elburzalis sp. n. from Iran. 58 records from Hemmerder Schelk (Unna). 38404 records from Fife Nature Records Centre combined dataset. 10 records from The harvestman genus Taracus Simon 1879, and the new genus Oskoron (Opiliones: Ischyropsalidoidea: Taracidae). 4 records from Annotated checklist of the false blister beetles (Coleoptera: Tenebrionoidea: Oedemeridae) from Iran. 5 records from New taxa and notes on crickets of the subfamily Landrevinae (Orthoptera: Gryllidae) from Brunei Darussalam, Borneo. 226 records from CHAS Botany Collection (Arctos). 1 records from First record of Gauguin's blunt-nose lizardfish, Trachinocephalus gauguini Polanco, Acero & Betancur 2016 (Teleostei: Synodontidae) outside the Marquesas Archipelago. 575 records from Total foraminifera counts of multinet M21/1_MSN604. 18 records from Description of two new species of Avicularia Lamarck 1818 and redescription of Avicularia diversipes (C. L. Koch 1842) (Araneae, Theraphosidae, Aviculariinae) - three possibly threatened Brazilian species. 16 records from New records of species of the Polyonyx sinensis group (Crustacea: Decapoda: Anomura: Porcellanidae) from Japan, the Philippines, Singapore, and Malaysia, with descriptions of two new species. 4056 records from Institut Botanic de Barcelona (IBB-CSIC-ICUB), BC-Lichen. 153 records from Plasm bearing foraminifera counts of multinet M21/5_MSN732. 2456 records from Diagnóstico del aprovechamiento de flora y fauna por los mayas del Ejido Petcacab y evaluación de la cacería y pesca, Felipe Carrillo Puerto, Quintana Roo. 240 records from Naturschutzgebiet Lochbusch-Königswiesen. 24 records from Integrative taxonomy reveals cryptic diversity in neotropical grasshoppers: taxonomy, phylogenetics, and evolution of the genus Sphenarium Charpentier, 1842 (Orthoptera: Pyrgomorphidae). 13 records from Two new deep-water species of the genus Thorogobius (Teleostei: Gobiidae) from the upper continental slope of the Eastern Central Atlantic. 1 records from Bolletino del Museo Civico di Storia Naturale di Verona, Botanica Zoologica [2000-]. 277 records from Programme de valorisation des zones humides chassées - volet Oiseaux. 24 records from Revision of the ant genus Streblognathus (Hymenoptera: Formicidae: Ponerinae).. 9 records from A new South American species of Palaeophileurus Kolbe (Coleoptera: Scarabaeidae: Dynastinae: Phileurini). 269 records from Odonata de Veracruz. 129 records from Range table from benthic foraminifers in ODP Hole 178-1097A. 412 records from BIRDRACE Niederlausitz-Team. 1 records from First record of Cephenniini on Christmas Island, with updated checklist of world Cephennomicrus species and summary of their distribution (Coleoptera, Staphylinidae, Scydmaeninae). 426 records from Chinese species of Pediobius Walker (Hymenoptera: Eulophidae). 300 records from Schulgarten Huttenheim (Philippsburg/Baden). 12 records from Occurrence of Anafroptilum Kluge 2012 (Ephemeroptera: Baetidae) in Oriental Region. 421 records from (Table 6) Abundance of silicoflagellates and ebridians in selected samples from ODP Hole 138-849B. 332 records from Poissons et Crustacés d'eau douce de la Martinique. 12428 records from Invasive species - Chinese mitten crab (Eriocheir sinensis) in Flanders, Belgium. 66 records from (Table 2) Abundance of benthic foraminifers of sediment core PS2247-1. 314 records from Loup 2009 présence régulière communale (réseau Loup-Lynx ONCFS). 2 records from Boraginaceae (Cynoglossum cherangauiense). 31 records from Abundance of epibenthic echinoderms at seafloor photography station POS196_1024. 60 records from Ptilophora variabilis Hartig, 1968, bona species, and description of Ptilophora nebrodensis sp. n. from Sicily (Lepidoptera, Notodontidae). 8 records from Description of a new species of Enispa Walker, 1866 (Lepidoptera: Erebidae, Boletobiinae) from Thailand. 245 records from Microplankton abundance at Station MARCH-1997-GN36199704601MSB02 in the euphotic zone of the Aegean Sea in spring 1997. Part 1 - diatoms. 1054 records from FPN-EH-AVES - Breeding Distribution of seabirds in Patagonia Argentina coast. 1182 records from Microplankton abundance in the euphotic zone of the Aegean Sea in September 1994. 3848 records from Caracterización de la vegetación en una zona delimitada en Cumbitara, La Llanada, Policarpa y Los Andes Sotomayor (Nariño), como insumo para la identificación de oportunidades de conservación para la recuperación de los servicios ecosistémicos de bosque seco. 73663 records from Grasshopper and Cricket (Orthoptera) and related species records from Britain and Ireland to 2007. 10 records from Gewässeruntersuchung (Prien) mit Kl. 4b. 19 records from Range table from planktonic foraminifers in ODP Hole 151-912A. 11 records from SNH Invertebrate Site Condition Monitoring of Beetle Assemblage Features 2015: Glen Tarff SSSI. 640839 records from VegetWeb - Repositorium von Vegetationsaufnahmen. 91 records from Zooplancton de sistemas acuáticos artificiales y naturales de Colombia. 27986 records from Bird records for Argyll for the years 2002 and 2003. 4227 records from Données naturalistes de Loïc SALAUN. 1139 records from SWECO. 1546 records from Ibaraki Nature Museum, Fish collection. 1718 records from (Appendix A) Radiolarian abundances in ODP Hole 175-1084A. 18 records from Range table from planktonic foraminifers in ODP Hole 182-1128D. 256 records from Fiocruz/CCAMP - Coleção de Campylobacter. 79125 records from EAC - Herbário Prisco Bezerra. 9 records from Distribution of Quinqueloculina sp. in sediment core 13077-023. 5014 records from East Ayrshire Species Database. 8 records from CNIN/Tipos Homoptera. 2016 records from Phytoplankton abundance in surface water in June 1997, Callao, Peru. 557 records from Otter (Lutra lutra), Outer Hebrides. 3278 records from Naturalis Biodiversity Center (NL) - Chelicerata and Myriapoda. 4 records from The male of the orb-weaving spider Plebs mitratus (Simon, 1895) and a redescription of the female (Araneae, Araneidae). 21 records from Sarcodine counts and carbon biomass at station TT011_6-CTD71. 3 records from A new genus and species of large-bodied caridean shrimp from the Crozet Islands, Southern Ocean (Crustacea, Decapoda, Lipkiidae) with a checklist of Antarctic and sub-Antarctic shrimps. 437 records from Benthic macrofauna abundance of subcores of sediment core 13078-015. 2146 records from Collection Crustacea - ZMB. 66 records from Range table from ostracoda in ODP Hole 151-910D. 874 records from The Living Murray Fish data. 3091868 records from SLU Aqua Institute of Freshwater Research National register of survey test-fishing - NORS. 178 records from (Fig. 3) Relative abundance of Neogloboquadrina pachyderma (s) in sediment core MD99-2343. 21 records from Sarcodine counts and carbon biomass at station TT007_7-CTD76. 709 records from Relevé de collections de lépidoptères rhopalocères et de coléoptères saproxyliques.. 23 records from Nematode genera abundances at the Arctic Håkon Mosby Mud Volcano (HMMV) of sediment core PS64/312-1. 140 records from Bishop's University Insect Collection (BUIC). 19 records from Two new species of Brueelia Kéler, 1936 (Ischnocera, Philopteridae) parasitic on Neotropical trogons (Aves, Trogoniformes). 210 records from Catalogue of the herbarium specimens collected from Discovery Bay and Runaway Bay, Jamaica, West Indies, 1958-1999.. 24 records from ALTERECO_2017_12_18. 161 records from Range table from planktonic foraminifers in ODP Hole 175-1084A. 3 records from New species of Prolachesilla Mockford & Sullivan (Psocodea: ‘ Psocoptera’: Lachesillidae: Graphocaeciliini) from Bolivia and Mexico. 446 records from Mean density of total metazoan meiofauna and major taxa or groups in the top 10 cm of surface sediment on 25 different dates at DYFAMED station. 30 records from Abundance, biovolume and biomass of heterotrophic dinoflagellates at station TT007_6-CTD67. 790729 records from BioFokus. 22189 records from Anymals+plants - Citizen Science Data. 1370 records from Arctic benthic invertebrate collection of the Zoological Institute of the Russian Academy of Science. 9384 records from Tartu University, palaeontology collections. 159 records from Living benthic foraminifera at station M33/1_MC-13 (WAST-T), size fraction 63-125 µm. 2 records from A new moss salamander, genus Nototriton (Caudata: Plethodontidae), from the Cordillera de Talamanca, in the Costa Rica-Panama border region. 1 records from New or little-known taxa of Anurophorinae (Collembola) with anal spines from East Asia with notes on DNA barcode. 6774 records from Données avifaune de Guadeloupe. 387 records from Benthic foraminiferal number, diversity, and species abundance of size fraction 63-125µm across sapropel S6 in core M40/4_KL51 from the lower bathyal of the western Levantine Basin. 12 records from Range table from planktonic foraminifers in ODP Hole 172-1057A. 210 records from UMNH Reptiles and Amphibians Collection (Arctos). 1600 records from Bryophytes Collection of National Museum of Nature and Science. 3 records from Gymnothorax pseudotile sp. nov. (Muraenidae: Muraeninae) from Bay of Bengal India. 1314 records from CNAN/Scorpiones. 54 records from Three new species of Anacharis Dalman, 1823 (Hymenoptera: Figitidae), with revised taxonomy and distribution records of Palaearctic and Indomalayan species. 2 records from A new species of the genus Pseudotrachystola Breuning (Coleoptera: Cerambycidae: Lamiinae) from China. 280 records from Total foraminifera counts of multinet M26/1_MSN845. 491 records from Plants, Bryophytes and Lichens recorded on the Nevis Estate during summer 2003.. 2560 records from (Table T1) Calcareous nannofossil stratigraphy of ODP Hole 198-1207A. 138 records from Assemblage of living benthic foraminifera in sediment core SO118_MC-51, 63-125 µm fraction. 61889 records from The fishes collection (IC) of the Muséum national d'Histoire naturelle (MNHN - Paris). 372 records from DBG Tissue and DNA Bank. 508 records from Range table from planktonic foraminifers in ODP Hole 155-930C. 228 records from BIRDRACE Di-Bi-Di-Birder. 22 records from Description of five new species of the genus Stigmaeus Koch (Acari: Raphignathoidea: Stigmaeidae) from Turkey. 264 records from (Fig. 2) Abundance of Neogloboquadrina pachyderma sinistral in sediment core MD95-2039. 19622 records from Colección, preservación y caracterización de cultivares criollos de origen español de trigo y centeno de México. 849 records from Collection de C.C.H. Jongkind aux Monts Nimba. 316 records from (Table 2) Palynological group observed in ODP Site 170-1039 samples. 150 records from Museo Provincial de Ciencias Naturales “Florentino Ameghino”, Santa Fe, Argentina - Colección Aves Nidos (MFA-ZV-Or-N). 2 records from Database_Dragonflies_ Madagascar Biodiversity Center PBZT. 417 records from HerbarioHerrerense. 8 records from Taxonomy of the Capensibufo rosei group (Anura: Bufonidae) from South Africa. 222 records from Nematode abundances in sediments from the Storegga Slide (Norwegian Sea) obtained during the VICKING expedition in 2006. 3 records from A revision of the subgenus Eurycercus (Teretifrons) Frey, 1975 (Crustacea: Cladocera) in the Holarctic with description of a new species from Russian Arctic. 5375 records from (Table 1) Stratigraphic distribution of dinocyst taxa in ODP Site 150-902. 14 records from A review of the ant genus Metapone Forel from Madagascar.. 341 records from Microzooplankton abundance measured on water bottle samples at station PS58/048-3. 109 records from Phytoplankton abundance at station Casma_2003-03-27_2, Casma, Peru. 86397 records from Mollusca of Costa Rica (INBio). 665 records from Total foraminifera counts of multinet SO118_MSN1253. 2 records from Two new species of Prionomastix Mayr (Hymenoptera: Encyrtidae) with a key to Indian species. 2 records from Phylloicus mirabilis (Trichoptera: Calamoceratidae), a new species from Rio de Janeiro state, southeastern Brazil. 47 records from Assemblage of living benthic foraminifera in sediment core SO119_MC501, 30-63 µm fraction. 11196 records from Macroinvertebrate abundance data from the littoral zone of a number of large New Zealand lakes. 4511 records from SPC PROCFish/C Invertebrates Observations Solomon Islands 2006. 3 records from Review of continental North and Central American Paracloeodes Day 1955 (Ephemeroptera: Baetidae), including description of a new species from Minnesota, U. S. A.. 1461 records from The Vascular Plants Collection of the University of Goettingen. 88 records from Numbers and statistics of benthic foraminiferal Q-mode assemblages for the Lower Oligocene of section Poetschbichl in the Lower Inn Valley area. 1788 records from Flora vascular acuática de la cuenca del Río Tamesí. 1385 records from Distribution of ostracoda in the Arctic Ocean (Table 1). 16 records from LSU Shirley C. Tucker Herbarium at Louisiana State University - Algae. 7068 records from Planktonic foraminifera, stable isotope record and temperature reconstruction of sediment core MD95-2040. 20 records from Ice Amphipods Canada Basin. 1 records from Two new goatfishes of the genus Upeneus (Mullidae) from Australia and Indonesia. 1588 records from flower availability 2008 Hainich. 252 records from Distribución y algunos aspectos ecológicos de hongos hidnoides estipitados de México. 4 records from Données naturalistes de Stéphane ORIO. 1911 records from Echigo-Matsunoyama Museum of Natural Science, Usuke Shiga butterfly collection. 11495 records from Andes to Amazon Biodiversity Program. 968 records from Miljodir_naturtypekartlegging_2017. 16 records from Two new species of Pamphobeteus Pocock 1901 (Araneae: Mygalomorphae: Theraphosidae) from Brazil, with a new type of stridulatory organ. 300 records from Inventario herpetofaunístico del noroeste de Hidalgo. 488 records from WildesMoor bei Schwabstedt. 1 records from The Paleontological Collections at the Bayerische Staatssammlung für Paläontologie und Geologie. 794 records from Diatom abundance measured on water bottle samples at station PS58/046-3. 2 records from Description of lithologic section units of IODP Hole 325-M0052A. 7 records from Microplankton abundance in the euphotic zone of the Aegean Sea at Station JUNE-1998-IR16. 150 records from Abundance of planktic foraminifera at CTD station M39/4_381CTD-34. 4 records from Studies on Dendrothripinae (Thysanoptera, Thripidae) from Japan, with new records and one new species. 20 records from Harpactus Shuckard. 1618 records from Los crustáceos decápodos marinos: Actualización de la colección carcinológica de la Facultad de Ciencias Biológicas, UANL. 8 records from Distribution of Quinqueloculina sp. in sediment core 13077-093. 2303 records from Jardín Botánico Atlántico, Gijón: JBAG. 62 records from Microzooplankton abundance and biomass at station TT045_26-3. 2838 records from Diversity of algae in wetlands. 2 records from Description of a new species of the Ponerine ant genus, Emeyopone (Hymenoptera: Formicidae) from Karnataka, India.. 832 records from Range table from planktonic foraminifers in ODP Hole 157-954A. 488 records from DREAL_PACA_-_N2000_-_GIP_Calanques_2017_12_18. 2 records from Trichomycterus giganteus (Siluriformes: Loricarioidea: Trichomycteridae): a new catfish from the Rio Guandu basin, southeastern Brazil.. 1414 records from (Table 1) Abundances of planktonic and benthic foraminifera in ODP Hole 130-806B. 72 records from Données sur les Opisthobranches et Planaires de Mayotte. 7 records from Microplankton counts and carbon biomass at station TT011_3-CTD33. 322 records from Estudio taxonómico de moluscos terrestres y dulceacuícolas de la región maya de México I. Reserva de la Biosfera Pantanos de Centla. 623 records from Range table from benthic foraminifers in ODP Hole 189-1169A. 10 records from SNH Invertebrate Site Condition Monitoring of Beetle Assemblage Features 2015: Taynish Woods SSSI. 3 records from Abundance of zooplankton in the Aral Sea. 105 records from Fish Fauna of Berlin. 7 records from Range table from planktonic foraminifers in ODP Hole 159-959D. 5 records from Five new species of the spider genus Pholcus Walckenaer, 1805 (Araneae: Pholcidae) from China and Thailand. 607 records from King penguin census data, Gadget Gully, Macquarie Island (1993-2008). 214 records from Biotop Binsenwiesen und Ernst-Reiter-Wiese (Wehrheim/Taunus). 2328 records from Phytoplankton abundance in surface water during cruise CD61. 83 records from Total foraminifera counts of trap L3_92_45. 1811 records from Colección de Herpetología del Instituto de Ciencias Naturales (ICN-MHN-Her). 28 records from Contribution to the knowledge of Cloeodes Traver 1938 (Ephemeroptera, Baetidae). 176 records from "Schlechteberg" Ebersbach/Sa.. 34 records from Phytoseiid mites (Acari: Phytoseiidae) associated with tropical ornamental plants, with a checklist and a key to the species of Bahia, Brazil. 374 records from Medicinal potential of African plants (Togo). 1766 records from Inventaire des Coléoptères Longicornes des Antilles françaises. 9896 records from Nijmegen Natural History Museum (NL) - Herbarium. 935 records from Collection des données de biodiversité marine de Polynésie française. 2 records from Two new species of amphipods (Crustacea: Amphipoda: Photidae) from Korean waters with a redescription of Gammaropsis longipropodi. 2 records from Scirtothrips genus-group in Iran with an unusual new species of Scirtothrips (Thysanoptera: Thripidae). 1 records from Anophtalmic and epigean? Description of an intriguing new species of Hyalella (Amphipoda, Hyalellidae) from Brazil. 3424635 records from Suffolk Biodiversity Information Service (SBIS) Dataset. 2 records from Three new species of Synagelides Strand, 1906 from China (Araneae: Salticidae). 52 records from Phylogeny of Corynoptera Winnertz and related genera, with the description of Claustropyga gen. nov. (Diptera, Sciaridae). 10 records from Données naturalistes de DURON Cyril. 4247 records from Collection Pisces SMF. 277 records from Microplankton abundance at Station SEPT-1997-GN36199704605MSB02 in the euphotic zone of the Aegean Sea in September 1997. Part 2 - dinoflagellates. 121584 records from Staffordshire Wildlife Trust Nature Reserves Inventory. 2 records from Omophorus (Sinomophorus) wallaCei: a new weevil from Borneo highlights the enigmatic Ethiopian-Oriental disjunct distribution (Coleoptera, Curculionidae, Molytinae). 2 records from Review of the genus Hannemania (Acari: Leeuwenhoekiidae) with description the two new species in amphibians from Chile. 10316 records from Herbarium specimens of Jardins botaniques and Conservatoire Botanique of Nancy (NCY). 1 records from Endemic Families of Madagascar. XIV. a New Restricted Range Species of Pentachlaena H. Perrier (Sarcolaenaceae) from Central Madagascar. 1802 records from Banco de Germoplama del Jardín Botánico de Castilla-La Mancha. 1680 records from MEXU/Tipos de plantas vasculares. 46 records from New state records and updated checklist of Aphodiini and Eupariini (Coleoptera: Scarabaeidae: Aphodiinae) from Mexico. 24 records from Redescription of Bomis larvata L. Koch, 1874 with the description of a new Australian species. 692 records from Packer Collection /Madagascar. 26 records from Rediscovery and redescription of Laelaps lignicola G. & R. Canestrini, a remarkable myrmecophilous mite of the genus Cosmolaelaps Berlese (Acari: Mesostigmata: Laelapidae) from Italy. 2223 records from Données de Lépidoptères de Bruno DAUGET - Dépt de l'ALLIER (03). 6 records from Ctenodontina Enderlein, 1914 (Diptera, Asilidae, Asilinae): new combinations, synonyms, new species and new records for Argentina. 17807 records from Condition of rocky reef communities around Tasmania: fish surveys, Australia (1992-1995 and 2006-2007). 2167 records from (Table 7) Distribution of dead benthic foraminifera in deep-sea surface sediments of the Scotia Sea, part 2. 876 records from Phytoplankton abundance off Chao island in Juli 2003, Peru. 152 records from (Table 15) Calcareous nannofossil occurrences in ODP Hole 130-805C. 15 records from A new genus and new species of freshwater crab (Decapoda: Brachyura: Potamidae Ortmann, 1896) from Yunnan Province, China. 3 records from Brasilisia n. gen. and Arraia n. gen., two new genera of Ocnerodrilidae (Annelida, Clitellata, Oligochaeta) from Eastern Amazonia, Brazil. 75 records from Conocimiento de la diversidad y distribución actual del maíz nativo y sus parientes silvestres en México. 6 records from Four new species of Phyllophaga Harris (Coleoptera: Scarabaeidae: Melolonthinae) from western Cuba. 156 records from Upper Tapanahony Expedition 1991. 1632 records from Phytoplankton abundance in surface water in November 1997, Pisco, Peru. 291 records from Abundance of broken diatom frustules measured on water bottle samples at station PS58/049-3. 228 records from Measurements of elephant tusk trophies taken in Botswana 1999. 4 records from A new species of Thalerosphyrus Eaton 1881 (Ephemeroptera: Heptageniidae: Ecdyonurinae) from India. 96734 records from TPWD HARC Texas Coastal Fisheries Matagorda Bay Trawl. 4676 records from Fish specimens of Natural History Museum, Kishiwada City. 458 records from Total foraminifera counts from multinet M31/2_MSN888. 2 records from Three new species of Grotea Cresson (Hymenoptera: Ichneumonidae: Labeninae) from Colombia. 8 records from A new species of Olecryptotendipes Zorina from China (Diptera, Chironomidae). 40 records from Benthic macrofauna abundance of sediment core 13078-013. 5 records from Redescription of Tapinesthis inermis (Araneae, Oonopidae), with detailed information on its ultrastructure. 13 records from Range table from planktonic foraminifers in ODP Hole 183-1136A. 194 records from FBIP:IZIKO-UCT:Historical Invertebrates (1930-1980). 564 records from Atewa Range Forest Reserve Bryophytes dataset, Ghana. 10 records from Colección de Referencia de Platelmintos del Museo de Ciencias de la Universidad El Bosque. 7 records from The publication of primary biological events in the international GBIF (Global Biodiversity Information Facility) network: A case study with a small dataset of field collected occurrence samples of Buriti palms (Mauritia flexuosa).. 1714 records from Field Study Group of the Dutch Mammal Society (NL) - 2004 - Mammal Survey Rakitovec, Slovenia. 1163 records from Fungi specimens of Saitama Museum of Natural History. 812 records from Relative abundance of ostracods in sediment core St09. 8 records from Taxonomic notes on Palearctic Podalonia Fernald, 1927 (Hymenoptera, Sphecidae), with descriptions of four new species. 25 records from New species and record of Nazeris Fauvel in southern China (Coleoptera, Staphylinidae, Paederinae). 74 records from Naturbelassene ehemalige Wiese am Haselbach (Privates Schutzgebiet). 8 records from Benthic hard-bottom communities abundance at X-Huinay, Comau Fjord, Chile, in 2010. 302 records from Microplankton abundance in the euphotic zone of the Aegean Sea in October-November 1991. 332 records from Mollusca Collection of Saitama Museum of Natural History. 7650 records from Nematode genera abundance from Portuguese canyons HERMES HERMIONE. 168 records from Range table from benthic foraminifers in ODP Hole 198-1214A. 129 records from Plasm bearing foraminifera counts of multinet M21/5_MSN734. 336 records from Range table from planktonic foraminifers in ODP Hole 155-945A. 36 records from BIOMEO_2017_12_18. 237 records from Range table from benthic foraminifers in ODP Hole 198-1209C. 5306 records from Phytoplankton abundance during ARGOS cruise Argos90/8. 1036 records from Fishes in MZNA-VERT: monitoring program in the Suspiro stream (Spain).. 6 records from New species of the spider genus Olios Walckenaer, 1837 (Araneae: Sparassidae: Sparassinae) from Laos. 1 records from A new species of Ninia (Serpentes: Dipsadidae) from Chocó-Magdalena biogeographical province, western Colombia. 78 records from (Table 10) Coiling ratio of Neogloboquadrina pachyderma of ODP Holes 127-794A and 127-197B. 1712 records from Benthic foraminiferal assamblage in the 125-250 micron fraction of sediment core PS1906-1 (Table 6). 1 records from Phoronida - SMF. 125 records from Determinación de la distribución potencial de las especies nativas e introducidas de bambú en México.. 8 records from A new species of Astyanax (Characiformes: Characidae) from the endorheic Río Salí basin, Tucumán, northwestern Argentina.. 479 records from Pollen counts of sediment core GeoB9503-5. 192 records from Living benthic foraminifera at station M33/1_MC-19 (CAST), size fraction >125 µm. 8 records from Nemertini - SMF. 8 records from Redescription of Seira pallidipes Reuter, 1895 and its synonymization with Seira pillichi Stach, 1930 (Collembola, Entomobryidae, Seirini). 393 records from Bosque Mesófilo de Montaña de México. 30 records from Abundance, biovolume and biomass of heterotrophic dinoflagellates at station TT011_10-CTD121. 331 records from 6. Tag der Artenvielfalt Hockenheim Thema: Wald 12.-14.6.2009. 106 records from New records of ants (Hymenoptera: Formicidae) from Iran.. 134 records from Weide an der Mosselde / Dortmund-Kirchlinde/Westerfilde. 18 records from Descriptions of two new species of Rhopalovalva Kuznetzov, 1964 (Lepidoptera: Tortricidae) from China. 1588 records from Macroarthropods, Narsarsuaq 2014, Greenland. 44 records from Microplankton counts and carbon biomass at station TT008_5-CTD25. 2 records from Amphibian specimens of Obihiro Centennial City Museum. 818 records from Records of fish species in coastal lagoons from Municipality of Arta, for the period 1999-2011. 194 records from Landschaftspark St.Leonhard-Deisendorf. 3934 records from Fototrampeo de sistemas cársticos en el municipio de El Peñón, Santander - Proyecto Colombia BIO. 45706 records from Données de Lépidoptères de Denis Vandromme. 140 records from Birdrace-WdW-Wilder_Westen-Viersen. 1037640 records from Parc_National_de_Port_Cros_2017_12_18. 9 records from Distribution of Quinqueloculina sp. in sediment core 13077-089. 252 records from Aix-Marseille Université - MARS herbarium – Cytogenetic data-base. 38211 records from University of Graz, Institute of Plant Sciences - Herbarium GZU. 1805 records from Diversidad y distribución de los copépodos (Cyclopoida) de las zonas áridas del Centro-Norte de México. 11 records from Morphology and molecular data reveal the presence of two new species under Rhamdia quelen (Quoy & Gaimard, 1824) (Siluriformes: Heptapteridae) species complex. 37 records from (Table T4) Calcareous nannofossil stratigraphy of ODP Hole 198-1208A. 10 records from New synonymy, new species, new keys to Neivamyrmex army ants of the United States.. 6758 records from MPM Milwaukee Public Museum Herbarium. 26 records from Trimma tevegae and T. caudomaculatum revisited and redescribed (Acanthopterygii, Gobiidae), with descriptions of three new similar species from the western Pacific. 30 records from Occurrence data of Anasillomos (Diptera: Asiloidea: Asilidae). 2 records from Collection ornithologique A. Maës. 60 records from Range table from planktonic foraminifers in ODP Hole 173-1068A. 1632 records from Determinación del estado actual de cinco especies de cactáceas amenazadas del estado de Tamaulipas, México. 1 records from Libnotes crane flies (Diptera: Limoniidae) from Jeju Island (South Korea). 5902 records from Actualización de la base de datos de diversidad taxonómica de las larvas de peces de Bahía Vizcaíno. 7 records from Minooa Yamanaka, 1996, a genus newly recorded to China with description of a new species (Lepidoptera, Pyralidae, Pyralinae). 21 records from Mammal specimens of Komatsu City Museum. 10 records from A new group of species within the bee genus Ruizantheda, with a revised key to the males of the genus (Hymenoptera: Halictidae: Caenohalictini). 85 records from Ecología de comunidades microbianas en las aguas subterráneas de Cuatrociénegas, Coahuila. 45 records from Review of the leafhopper genus Anufrievia Dworakowska (Hemiptera: Cicadellidae: Typhlocybinae: Erythroneurini). 540 records from ACT and Southern Tablelands Weed Spotter. 174 records from Brachycera (Diptera) records from Britain and Ireland to 1990. 82 records from Örtzemündung (Stedden). 909 records from Dinámica poblacional de la tortuga de carey (Eretmochelys imbricata) en su área de forraje. Río Lagartos, Yucatán. 849 records from Diatom abundance measured on water bottle samples at station PS58/042-2. 143 records from Range table from planktonic foraminifers in ODP Hole 160-966F. 5771 records from Segunda caracterización biológica de plantas del proyecto "Incorporación de la Biodiversidad en el sector cafetero en Colombia". 58913 records from National Stag Beetle Surveys (Great Stag Hunts). 609 records from (Appendix 8) Stable oxygen isotope record of Globigerina bulloides, and abundances of Neogloboquadrina pachyderma and ice-rafted debris in sediment core MD99-2339. 86676 records from Marine Offshore Seabed Survey data held by JNCC. 29162 records from KUBI Ornithology Collection. 260 records from Nanoplankton abundance at station GeoB2006-4. 86 records from Données naturalistes de Françoise SERRE-COLLET. 425 records from (App 5) Relative contents of benthic foraminifera species in Holocene sediments from Core BP01-62/04. 10264 records from Natural History Museum Rotterdam (NL) - Chordata collection. 2244 records from Range table from planktonic foraminifers in ODP Hole 144-872C. 4 records from Description of two new species and phylogenetic reassessment of Perelleschus O’Brien & Wibmer, 1986 (Coleoptera: Curculionidae), with a complete taxonomic concept history of Perelleschus sec. Franz & Cardona-Duque, 2013. 7 records from (Table 7) Fatty acid comp
Keywords: GBIF; biodiversity; species occurrences